Asymmetric stress profile for low warpage and high destruction resistance glass articles
By creating an asymmetric stress distribution on different surfaces of glass products, the warping problem during chemical strengthening is solved, resulting in glass products with low warping and high resistance to damage, suitable for covers or windows of electronic devices.
Patent Information
- Application Number
- CN202411322009.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-03-02
- Filing Date
- 2018-03-01
- Publication Date
- 2025-01-07
AI Technical Summary
Existing glass products are prone to warping during chemical strengthening processes, and different surfaces have different stress requirements, making it impossible to effectively protect each surface from different types of damage.
An asymmetric stress distribution design is adopted, and different compressive stress distributions are formed on different surfaces of the glass product through ion exchange and heat treatment, ensuring low warpage and meeting the strengthening requirements of each surface.
This technology enables glass products with low warpage and high resistance to damage, improves the stress resistance of glass products on different surfaces, and enhances their reliability in electronic devices.
Smart Images

Figure CN119263650A_ABST
Abstract
Description
[0001] This invention patent application is a divisional application of the invention patent application with application date of March 1, 2018, application number of 202210916544.7, and invention name of “Asymmetric stress distribution of low warpage and high damage resistance glass products”. The above invention patent application is also a divisional application of the invention patent application with international application number of PCT / US2018 / 020413, international application date of March 1, 2018, application number of 201880015453.8 in the Chinese national phase, and invention name of “Asymmetric stress distribution of low warpage and high damage resistance glass products”.
[0002] Related Applications
[0003] This application claims the benefit of U.S. Provisional Application Serial No. 62 / 466,240, filed on March 2, 2017, which is based upon and incorporated herein by reference in its entirety. Background Art
[0004] The present disclosure relates to a glass article having an asymmetric stress distribution. More particularly, the present disclosure relates to a chemically strengthened glass article including an asymmetric stress distribution with low warpage.
[0005] Glass products are widely used in electronic devices as covers or windows for portable or handheld electronic communication and entertainment devices, such as mobile phones, smart phones, tablets, video players, information terminal (IT) devices and tablet computers, etc., as well as other applications. As glass products become more and more widely used, it becomes increasingly important to create strengthened glass products with improved durability, especially when subjected to tensile stresses and / or deeper flaws caused by contact with hard and / or sharp surfaces. In addition, the main failure modes of various surfaces of glass products are different, and therefore, different strengthening characteristics are suitable for increasing the survivability of various surfaces of glass products. In order to achieve such different chemical strengthening characteristics on the surface of the glass product, an asymmetric stress distribution is adopted.
[0006] Asymmetric stress distribution of the type known in the art induces warping in glass articles. Warping in glass articles beyond a low degree renders the glass articles unsuitable for use as covers or windows for portable or mobile electronic communication and entertainment devices. Therefore, there is a need for glass articles having asymmetric stress distribution and low warping. Summary of the invention
[0007] Aspect (1) of the present disclosure provides a glass product comprising: a first surface; a second surface; an asymmetric stress distribution extending from the first surface to the second surface; a warpage figure of merit of the asymmetric stress distribution of at least about 0.5 m; and an asymmetry figure of merit of the asymmetric stress distribution of at least about 0.05.
[0008] Aspect (2) of the present disclosure provides a glass product comprising: a first surface; a second surface; an asymmetric stress distribution extending from the first surface to the second surface; a warpage tendency (Warpage Tendency) of the asymmetric stress distribution less than about 1 / 12 of the thickness of the glass product; and an asymmetry figure of merit (Asymmetry Figure of Merit) of the asymmetric stress distribution of at least about 0.05.
[0009] Aspect (3) of the present disclosure provides a glass article comprising: a first surface; a second surface; an asymmetric stress distribution extending from the first surface to the second surface; and an asymmetry figure of merit of the asymmetric stress distribution of at least about 0.05.
[0010] Aspect (4) of the present disclosure provides a glass article comprising: a first surface; a second surface; an asymmetric stress distribution extending from the first surface to the second surface; and a warpage tendency (Warpage Tendency) of the asymmetric stress distribution is less than about 1 / 12 of the thickness of the glass article.
[0011] Aspect (5) of the present disclosure provides a glass article comprising: a first surface; a second surface; an asymmetric stress distribution extending from the first surface to the second surface; and a warpage figure of merit of the asymmetric stress distribution of at least about 0.5 m.
[0012] Aspect (6) of the present disclosure provides the glass article of any of the preceding aspects, further comprising about 2-20 mol % B2O3.
[0013] Aspect (7) of the present disclosure provides a glass product of any of the preceding aspects, further comprising approximately 50-75 mol % SiO2, 5-20 mol % Al2O3, 2-20 mol % B2O3, 0-10 mol % P2O5, 6-25 mol % Li2O+Na2O+K2O, and 0-15 mol % MgO+CaO+SrO+BaO+ZnO.
[0014] Aspect (8) of the present disclosure provides the glass article of any of the preceding aspects, wherein the warpage figure of merit of the asymmetric stress distribution is at least about 1 m.
[0015] Aspect (9) of the present disclosure provides the glass article of any of the preceding aspects, wherein the warpage figure of merit of the asymmetric stress distribution is at least about 10 m.
[0016] Aspect (10) of the present disclosure provides the glass article of any of the preceding aspects, wherein the asymmetric stress distribution has an asymmetry figure of merit of at least about 0.2.
[0017] Aspect (11) of the present disclosure provides the glass article of any of the preceding aspects, wherein the asymmetric stress distribution has an asymmetry figure of merit of at least about 0.5.
[0018] Aspect (12) of the present disclosure provides the glass article of any of the preceding aspects, further comprising a compressive stress of at least about 500 MPa at a depth of less than 10 um below the second surface.
[0019] Aspect (13) of the present disclosure provides the glass article of any of the preceding aspects, further comprising a compressive stress of at least about 650 MPa at a depth of less than 5 um below the second surface.
[0020] Aspect (14) of the present disclosure provides the glass article of any of the preceding aspects, further comprising a compressive stress of at least about 40 MPa at a depth less than 10% of the distance between the first surface and the second surface below the first surface.
[0021] Aspect (15) of the present disclosure provides the glass article of any of the preceding aspects, further comprising a compressive stress of at least about 30 MPa at a depth less than 15% of the distance between the first surface and the second surface below the first surface.
[0022] Aspect (16) of the present disclosure provides the glass article of any of the preceding aspects, further comprising a radius of curvature of at least about 12.5 m.
[0023] Aspect (17) of the present disclosure provides a glass article of any of the aforementioned aspects, further comprising: a first compressive stress layer extending from the first surface to a first compressive depth in the glass article; a second compressive stress layer extending from the second surface to a second compressive depth in the glass article; a first maximum compressive stress in the first compressive stress layer; a second maximum compressive stress in the second compressive stress layer, wherein a ratio of the first maximum compressive stress to the second maximum compressive stress is less than or equal to about 1:3.
[0024] Aspect (18) of the present disclosure provides the glass article of any of the preceding aspects, wherein the glass article has a Warpage Suppression Factor of less than about 0.3.
[0025] Aspect (19) of the present disclosure provides the glass article of any of the preceding aspects, wherein the distance between the first surface and the second surface is less than about 1 mm.
[0026] Aspect (20) of the present disclosure provides the glass article of any of the preceding aspects, wherein the glass article comprises a region extending from the first surface to the second surface having a second stress distribution, and the second stress distribution is different from the asymmetric stress distribution.
[0027] Aspect (21) of the present disclosure provides the glass article of aspect (20), wherein the difference between the asymmetry figure of merit of the asymmetric stress distribution and the asymmetry figure of merit of the second stress distribution is at least 0.2.
[0028] Aspect (22) of the present disclosure provides the glass article of any of the preceding aspects, further comprising a glass ceramic.
[0029] Aspect (23) of the present disclosure provides the glass article of any of the preceding aspects, wherein the glass article is a laminate structure including at least a first layer and a second layer, and the first layer and the second layer each include glass or glass ceramic.
[0030] Aspect (24) of the present disclosure provides a consumer electronic product comprising: a housing having a front surface, a back surface, and side surfaces; an electronic component provided to be at least partially located within the housing, the electronic component comprising at least a controller, a memory, and a display, the display provided to be located on the front surface of the housing or adjacent to the front surface of the housing; and a covering glass product arranged above the display, wherein at least a portion of the housing or the covering glass product comprises the glass product of any of the aforementioned aspects.
[0031] Aspect (25) of the present disclosure provides a glass article comprising: a first surface; a second surface; an asymmetric stress distribution extending from the first surface to the second surface; a first compressive stress layer extending from the first surface to a first compression depth in the glass article; a second compressive stress layer extending from the second surface to a second compression depth in the glass article; and a warp height, wherein a ratio of the first compression depth to the second compression depth is at least about 1.5:1, and the warp height is less than about 1% of a maximum dimension of the glass article.
[0032] Aspect (26) of the present disclosure provides the glass article of aspect (25), which further includes: a first maximum compressive stress in the first compressive stress layer; a second maximum compressive stress in the second compressive stress layer, wherein a ratio of the first maximum compressive stress to the second maximum compressive stress is less than or equal to about 1:3.
[0033] Aspect (27) of the present disclosure provides the glass article of aspect (25) or (26), wherein the ratio of the first compression depth to the second compression depth is at least about 3:1.
[0034] Aspect (28) of the present disclosure provides the glass article of any one of aspects (25) to (27), wherein the warp height is less than about 0.1% of the largest dimension of the glass article.
[0035] Aspect (29) of the present disclosure provides the glass article of any one of aspects (25) to (28), wherein the glass article has an asymmetry figure of merit of at least about 0.2.
[0036] Aspect (30) of the present disclosure provides the glass article of any one of aspects (25) to (29), wherein the glass article has a Warpage Figure of Merit of at least about 0.5 m.
[0037] Aspect (31) of the present disclosure provides the glass article of any one of aspects (25) to (30), wherein the glass article has a Warpage Suppression Factor of less than about 0.3.
[0038] Aspect (32) of the present disclosure provides the glass article of any one of aspects (25) to (31), further comprising a compressive stress of at least about 500 MPa at a depth of less than 10 um below the second surface.
[0039] Aspect (33) of the present disclosure provides the glass article of any one of aspects (25) to (32), further comprising a compressive stress of at least about 650 MPa at a depth of 5 um below the second surface.
[0040] Aspect (34) of the present disclosure provides the glass article of any one of aspects (25) to (33), further comprising a compressive stress of at least about 40 MPa at a depth less than 10% of the distance between the first surface and the second surface below the first surface.
[0041] Aspect (35) of the present disclosure provides the glass article of any one of aspects (25) to (34), further comprising a compressive stress of at least about 30 MPa at a depth less than 15% of the distance between the first surface and the second surface below the first surface.
[0042] Aspect (36) of the present disclosure provides the glass article of any one of aspects (25) to (35), wherein the distance between the first surface and the second surface is less than about 1 mm.
[0043] Aspect (37) of the present disclosure provides the glass article of any one of aspects (25) to (36), further comprising a radius of curvature of at least about 12.5 m.
[0044] Aspect (38) of the present disclosure provides the glass article of any one of aspects (25) to (37), further comprising a glass ceramic.
[0045] Aspect (39) of the present disclosure provides the glass article of any one of aspects (25) to (38), wherein the glass article is a laminated structure including at least a first layer and a second layer, and the first layer and the second layer respectively include glass or glass ceramic.
[0046] Aspect (40) of the present disclosure provides a consumer electronic product comprising: a housing having a front surface, a back surface, and side surfaces; an electronic component provided to be at least partially located within the housing, the electronic component comprising at least a controller, a memory, and a display, the display provided to be located on the front surface of the housing or adjacent to the front surface of the housing; and a covering glass product arranged above the display, wherein at least a portion of the housing or the covering glass product comprises the glass product of any one of aspects (25) to (39).
[0047] Aspect (41) of the present disclosure provides a method comprising: performing ion exchange on a first surface of a glass article to form a first compressive stress layer extending from the first surface; performing ion exchange on a second surface of the glass article to form a second compressive stress layer extending from the second surface, wherein the glass article including the first compressive stress layer and the second compressive stress layer comprises: a warpage figure of merit of at least about 0.5 μm, and an asymmetry figure of merit of at least about 0.05.
[0048] Aspect (42) of the present disclosure provides the method of aspect (41), further comprising heat treating the glass article.
[0049] Aspect (43) of the present disclosure provides the method of aspect (41) or (42), wherein the first compressive stress layer and the second compressive stress layer are formed simultaneously.
[0050] Aspect (44) of the present disclosure provides the method of any one of aspects (41) to (43), further comprising: forming a barrier layer at the first surface of the glass article before ion exchanging the second surface.
[0051] Aspect (45) of the present disclosure provides the method of aspect (44), wherein forming the barrier layer comprises: ion exchanging the first surface with at least one of Cu, Ca, Mg, Zn and Ti ions.
[0052] Aspect (46) of the present disclosure provides the method of aspect (44) or (45), wherein the depth of the barrier layer is less than 1 um.
[0053] Aspect (47) of the present disclosure provides the method of any one of aspects (44) to (46), further comprising removing the barrier layer from the glass article.
[0054] Aspect (48) of the present disclosure provides the method of any one of aspects (41) to (47), further comprising: heat treating the glass article to form a curved glass article before ion exchanging the glass article.
[0055] Aspect (49) of the present disclosure provides a method comprising: disposing a salt on at least a portion of a first surface of a glass article; ion exchanging the glass article by heating the glass article and the salt to an ion exchange temperature to produce a glass article having an asymmetric stress distribution, wherein the salt includes a solid component that is solid at the ion exchange temperature.
[0056] Aspect (50) of the present disclosure provides the method of aspect (49), wherein the salt further comprises a liquid component that is liquid at the ion exchange temperature.
[0057] Aspect (51) of the present disclosure provides the method of aspect (49) or (50), wherein the salt component comprises at least one of an alkaline sulfate and an alkaline phosphate.
[0058] Aspect (52) of the present disclosure provides the method of any one of aspects (49) to (51), wherein the solid component comprises at least one of tripotassium phosphate, trisodium phosphate, potassium sulfate, and sodium sulfate.
[0059] Aspect (53) of the present disclosure provides the method of any one of aspects (49) to (52), wherein the liquid component comprises at least one alkaline nitrate.
[0060] Aspect (54) of the present disclosure provides the method of any one of aspects (50) to (53), wherein the liquid component comprises at least one of KNO3 and NaNO3.
[0061] Aspect (55) of the present disclosure provides the method of any one of aspects (49) to (54), wherein the amount of the solid component present in the salt is 5-99.5 wt%.
[0062] Aspect (56) of the present disclosure provides the method of any one of aspects (49) to (55), wherein the amount of the solid component present in the salt is 30-98 wt%.
[0063] Aspect (57) of the present disclosure provides the method of any one of aspects (49) to (56), wherein the salt is disposed on the entire first surface.
[0064] Aspect (58) of the present disclosure provides the method of any one of aspects (49) to (57), wherein the salt is not disposed on the center of the first surface.
[0065] Aspect (59) of the present disclosure provides the method of any one of aspects (49) to (58), wherein the salt is disposed only at the periphery of the first surface.
[0066] Aspect (60) of the present disclosure provides the method of any one of aspects (49) to (59), further comprising: forming a barrier layer on a portion of the first surface before disposing the salt.
[0067] Aspect (61) of the present disclosure provides the method of aspect (60), wherein the barrier layer comprises at least one of alkali-free glass, SiO2, and metal.
[0068] Aspect (62) of the present disclosure provides the method of aspect (60) or (61), further comprising removing the barrier layer after ion exchanging the glass article.
[0069] Aspect (63) of the present disclosure provides the method of any one of aspects (49) to (62), further comprising contacting the glass article with a molten salt bath.
[0070] Aspect (64) of the present disclosure provides the method of aspect (63), further comprising contacting the glass article with a second molten salt bath.
[0071] Aspect (65) of the present disclosure provides the method of any one of aspects (49) to (64), wherein the asymmetric quality factor (Asymmetry Figure of Merit) of the asymmetric stress distribution is at least about 0.05.
[0072] Aspect (66) of the present disclosure provides the method of any one of aspects (49) to (65), wherein the warpage figure of merit of the asymmetric stress distribution is at least about 0.5 m.
[0073] Aspect (67) of the present disclosure provides the method of any one of aspects (49) to (66), wherein the warpage tendency of the asymmetric stress distribution is less than about 1 / 12 of the thickness of the glass article.
[0074] These and other aspects, advantages and salient features will be apparent from the following detailed description, the accompanying drawings and the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 is a schematic cross-sectional view of a glass article according to one or more embodiments;
[0076] Figure 2 The stress-depth relationship of a theoretical ion-exchange glass product is shown;
[0077] Figure 3 Represents the stress versus depth relationship for a theoretical ion exchange glass article with an asymmetric stress distribution;
[0078] Figure 4 represents the stress versus depth relationship for a theoretical ion exchange glass article having an asymmetric stress distribution without warpage;
[0079] Figure 5 yes Figure 4 Symmetric and antisymmetric components of asymmetric stress distribution without warping;
[0080] Figure 6 representing the stress versus depth relationship for a theoretical ion-exchanged glass article having an asymmetric stress distribution, for which a spherical curvature is applied prior to ion exchange;
[0081] Figure 7 yes Figure 6 Evolution of the normalized concentration profile of a theoretical ion exchange glass at various steps in the ion exchange process;
[0082] Figure 8 yes Figure 6 an antisymmetric component of the asymmetric stress distribution of the glass article and an auxiliary component obtained by combining a spherical curvature to the glass article prior to ion exchange;
[0083] Fig. 9 yes Figure 6 Symmetric and antisymmetric components of the free asymmetric stress distribution;
[0084] Fig.10 is a front plan view of a consumer electronic product including an alkali aluminosilicate glass article according to one or more embodiments described herein;
[0085] Fig.11 yes Fig.10 A perspective schematic diagram of a consumer electronic product;
[0086] Fig.12 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0087] Fig.13 yes Fig.12 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0088] Fig.14 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0089] Fig.15 yes Fig.14 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0090] Fig.16 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0091] Fig.17 yes Fig.16 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0092] Fig.18 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0093] Fig.19 yes Fig.18 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0094] Fig. 20 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0095] Fig.21 yes Fig. 20 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0096] Fig. 22 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0097] Fig.23 yes Fig. 22 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0098] Fig.24It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0099] Fig.25 yes Fig.24 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0100] Fig.26 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0101] Fig. 27 yes Fig.26 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0102] Fig.28 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0103] Fig.29 yes Fig.28 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0104] Fig.30 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0105] Fig.31 yes Fig.30 Diagonal warping diagram of the sample at various stages of the ion exchange process;
[0106] Fig.32 is a plot of stress versus distance from the surface of the ion-exchanged glass article;
[0107] Fig.33 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0108] Fig.34 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0109] Fig.35 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0110] Fig.36 It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0111] Fig.37It is a cross warp diagram of the sample at various stages of the ion exchange process;
[0112] Fig.38 It is a cross warp diagram of the sample at various stages of the ion exchange process. DETAILED DESCRIPTION
[0113] In the following description, the same reference numerals represent similar or corresponding parts in several views shown in the accompanying drawings. It should also be understood that, unless otherwise specified, terms such as "top", "bottom", "outward", "inward", etc. are convenient words and do not constitute a restriction on the terms. In addition, whenever a group is described as comprising at least one element in a group of elements and their combination, it should be understood that the group can contain any number of these listed elements in the form of a single element or a combination of them, or mainly consist of them, or consist of them. Similarly, whenever a group is described as consisting of at least one element in a group of elements or their combination, it should be understood that the group can consist of any number of these listed elements in the form of a single element or a combination of them. Unless otherwise specified, the numerical range listed includes the upper and lower limits of the range at the same time, as well as any range between the ranges. Unless otherwise specified, the indefinite article "one" or "a kind" used herein and its corresponding definite article "the" mean "at least one (one / kind)" or "one (one / kind) or more (one / kind)". It should also be understood that the various features disclosed in the specification and drawings can be used in any and all combinations.
[0114] As used herein, the terms "glass articles" are used in their broadest sense and include any object made in whole or in part of glass (including glass ceramics). Unless otherwise specified, all components of the glasses described herein are expressed in mole percent (mol%), and the composition is in terms of oxides. Unless otherwise specified, all temperatures are expressed in degrees Celsius (°C). The term "liquidus viscosity" refers to the viscosity of a molten glass at the liquidus temperature, wherein the liquidus temperature refers to the temperature at which crystals first appear as the molten glass cools from the melting temperature, or the temperature at which the last bit of crystals melts as the temperature increases from room temperature.
[0115] It should be noted that the terms "substantially" and "about" may be used herein to represent the degree of uncertainty inherent in any quantitative comparison, value, measurement, or other representation. These terms are also used herein to represent the degree to which a quantitative representation may vary from a stated reference value without resulting in a change in the basic function of the subject matter at issue. For example, a glass that is substantially free of "K2O" is a glass in which K2O is not actively added or dosed into the glass, but may be present in very small amounts as a contaminant.
[0116] The Young's modulus values stated in this disclosure refer to values measured by resonant ultrasonic spectroscopy techniques of the general type set forth in ASTM E2001-13, entitled "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts."
[0117] The units of coefficient of thermal expansion (CTE) are parts per million (ppm) / °C and are expressed over a temperature range of about 20-300°C, unless otherwise stated. The high temperature (or liquid) coefficient of thermal expansion (high temperature CTE) is also expressed as parts per million (ppm) / degree Celsius (ppm / °C) and is expressed over the high temperature plateau region of the transient coefficient of thermal expansion (CTE) versus temperature curve. The high temperature CTE measures the volume change associated with heating or cooling the glass through a transition region. As used herein, the term "softening point" refers to the viscosity of a glass of about 10 7.6 The term "annealing point" refers to the temperature at which the viscosity of the glass is about 10 13.2 The term "200 poise temperature (T 200P )" refers to the temperature at which the viscosity of glass is about 200 poise. The term "10 11 The "Poise temperature" refers to the viscosity of the glass is about 10 11 The term "35kP temperature (T 35kP )” refers to the temperature at which the viscosity of the glass is about 35 kilopoise (kP), and the term “160 kP temperature (T 160kP )" refers to the temperature at which the viscosity of the glass is about 160 kP. As used herein, the term "zircon decomposition temperature" or "T 分解 ” refers to the temperature at which zircon, a commonly used refractory material in glass processing and manufacturing, decomposes to form zirconium oxide and silicon oxide, and the term “zircon decomposition viscosity” refers to the viscosity of glass at T 分解 The term “35 kP temperature” or “T 35kP ” refers to the temperature at which the viscosity of glass or glass melt is 35,000 poise (P) or 35 kilopoise (kP).
[0118] Compressive stress (including surface CS) is measured by a surface stress meter (FSM), using a commercial instrument such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurements rely on accurate measurements of the stress-optical coefficient (SOC), which is related to the birefringence of the glass. The SOC is then measured according to Protocol C (Glass Disc Method) described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the entire text of which is incorporated herein by reference. The maximum tensile stress or central tension (CT) value is measured using a scattered light polarizer (SCALP) as known in the art.
[0119] As used herein, depth of compression (DOC) represents the depth at which stress in the chemically strengthened aluminosilicate glass articles described herein changes from compression to tension. Depending on the ion exchange treatment, DOC can be measured by FSM or scattered light polariscope (SCALP). When stress is induced in the glass article by exchanging potassium ions into the glass article, FSM is used to measure DOC. When stress is induced in the glass article by exchanging sodium ions into the glass article, SCALP is used to measure DOC. When stress is induced in the glass by exchanging both potassium ions and sodium ions into the glass, DOC is measured by SCALP because it is believed that the depth of exchange of sodium represents the DOC, and the depth of exchange of potassium ions represents the change in the magnitude of the compressive stress (rather than the change of stress from compression to tension); in such glass articles, the depth of exchange of potassium ions is measured by FSM.
[0120] The penetration depth of K+ ions ("potassium DOL") is different from DOC because it represents the penetration depth of potassium as a result of the ion exchange process. For the articles described herein, the potassium DOL is generally less than the DOC. The potassium DOL is measured using a surface stress gauge (e.g., a commercially available FSM-6000 surface stress gauge manufactured by Orihara Industrial Co., Ltd. (Japan)), which relies on the accurate measurement of the stress optical coefficient (SOC), as described above for the CS measurement.
[0121] See the accompanying drawings in general and the Figure 1It should be understood that the examples are for the purpose of describing the specific embodiments of the present disclosure, and these examples are not intended to limit the specification of the present disclosure or the appended claims. For the sake of clarity and conciseness, the drawings are not necessarily drawn to scale, and some features and some views of the drawings may be shown in a scaled-up or schematic manner.
[0122] Although in Figure 1 In the described embodiments, the glass article 100 is shown as a flat planar sheet or plate, but the glass article can have other configurations, such as a three-dimensional shape or a non-planar configuration. The glass article 100 has a first surface 110 and a second surface 112, defining a thickness t. In one or more embodiments, (e.g., Figure 1 In the embodiment shown), the glass article is a sheet including a first surface 110 and an opposite second surface 112, defining a thickness t. The glass article 100 has a first compressive layer 120 extending from the first surface 110 to a layer depth d1 into the body of the glass article 100. Figure 1 In the illustrated embodiment, the glass article 100 also has a second compressive layer 122 extending from the second surface 112 to a second layer depth d2. The glass article 100 also has a central region 330 extending from d1 to d2. The central region 130 is in a tensile stress or central tension (CT) that balances or counteracts the compressive stresses of the layers 120 and 122. The depths d1, d2 of the first and second compressive layers 120, 122 protect the glass article 100 from flaw propagation caused by sharp impacts to the first and second surfaces 110, 112 of the glass article 100, while the compressive stress minimizes the likelihood of flaws penetrating through the depths d1, d2 of the first and second compressive layers 120, 122. The depths d1 and d2 may be the same or different from each other and are related to the depth of compression (DOC) of the compressive layers.
[0123] Figure 2 Shows the theoretical stress distribution of a portion of an ion-exchanged glass article. Figure 2 The stress distribution shown includes compressive stress spikes at the surface and deeper diffusion regions. Figure 2 As shown, the compressive stress (CSk) at the inflection point of the stress distribution is the transition between the peak portion of the stress distribution and the deeper diffusion region of the stress distribution. Fig. 9 Also shown are DOC and potassium DOL, which is simply labeled DOL.
[0124] The glass articles described herein have an asymmetric stress distribution that exhibits a lower degree of warpage after being strengthened. The asymmetric stress distribution allows the surfaces of the glass article to exhibit different strengthening characteristics, thereby addressing the dominant failure mode at each surface while also minimizing undesirable warpage in the glass article.
[0125] For example, glass articles used as cover glass in consumer electronic devices have a front surface (exposed surface), a back surface, and an edge surface. During use, the cover glass is subjected to different service stresses on the front surface, the back surface, and the edge surface.
[0126] The main failure mode on the front surface is usually due to the introduction of deep flaws and the exposure of deep flaws to tension. Deep flaws may be exposed to tension when they extend to the depth of the tensile stress layer or when the glass article is flexed. The main failure mode on the front surface can be solved by deep compression depth to prevent the introduced flaws from experiencing tension.
[0127] The primary failure mode on the back surface is typically overstressing of pre-existing shallow defects. Shallow defects are typically shallower than 10 um, more typically shallower than 5 um. Overstress typically exceeds tensile stress by hundreds of megapascals (MPa), for example, greater than about 500 MPa. Overstress may be the result of flexing of the glass article during use. The primary back surface failure mode may be addressed by a high compressive stress spike on the back surface (e.g., a spike with a compressive stress greater than about 500 MPa and a spike depth exceeding about 8 microns).
[0128] The edge surface of the cover glass is exposed in some applications and protected by a bevel in other applications. The edge surface may be subjected to very significant stress when dropped onto a harder surface. Therefore, high surface compressive stress and high compressive stress at a depth of several microns can also reduce the possibility of cracking originating from the edge surface of the cover glass.
[0129] Due to the difference in strengthening properties that address the primary failure modes of the front and back surfaces, different strengthening properties can be imparted by forming an asymmetric stress profile across the thickness of the glass article, which provides improved performance compared to a symmetric stress profile that does not fully address at least one of the primary failure modes of the front and back surfaces. The asymmetric profile can have: higher compression depth and higher stress at large depths on the front surface, and higher surface compressive stress (CS) on the back surface and higher compressive stress in the first about 5-10 microns below the surface. The edge of the cover glass can also have higher surface compressive stress and higher stress in the first about 10 microns below the surface.
[0130] Asymmetric stress distribution can cause warping of glass articles, which is problematic for assembly, and can also cause stress changes during assembly, which can negatively affect the strength of the glass article during use. Methods are described herein that can reduce the warping caused by tempering or strengthening to negligible levels through proper design of the asymmetric stress distribution, which also provides the desired strengthening properties at the front and back surfaces of the glass article.
[0131] A tempered or chemically strengthened glass article in a stable mechanical state (not shrinking or expanding, and not bending or warping) satisfies force balance and torque balance. Force balance requires that the total integrated compressive stress in the compression region through the thickness equals the total integrated tensile stress in the tension region through the thickness (in absolute value), as shown in the following equation (1):
[0132]
[0133] Where σ is stress and x is the position along the thickness of the glass article, with x=0 representing the mid-plane (center) of the glass article. This is equivalent to setting the stress integral over the thickness equal to zero, as shown in equation (2):
[0134]
[0135] Torque balance means that the stress distribution of the glass product does not induce warping. Torque balance requires that the integral of the local stress in the thickness multiplied by the local arm length is equal to zero, as shown in the following equation (3):
[0136]
[0137] In equation (3), x also represents the local arm length used to calculate the specific torque per unit depth change due to local stress.
[0138] A stress distribution that is symmetric with respect to x does not result in distribution-induced warping. For example, in ion exchange of flat specimens (where the glass article is immersed in a molten salt and exchanged to the same surface compression and the same depth of layer around the entire article), negligible warping is typically produced.
[0139] If the stress distribution is asymmetric, it may satisfy the force equation (2) during and after the ion exchange, but if the zero torque condition is not satisfied, the glass article may experience stress distribution induced warping. Generally speaking, the more asymmetric the stress distribution, the greater the stress distribution induced warping. At the same time, asymmetric distributions with greater asymmetry may produce greater benefits in reducing the likelihood of cracking due to the more significant increase in stress at the large compression depth on the front surface and the large compressive stress on the back surface achieved with the DOC.
[0140] To resolve this contradiction, the general asymmetric distribution can be decomposed into two components according to the following equation (4): s (x)) and the antisymmetric component (σ a (x)):
[0141] σ(x)=σ s (x)+σ a (x)
[0142] Here, σ is defined by the following equation (5): s (x):
[0143]
[0144] and where σ is defined by equation (6) a (x):
[0145]
[0146] The antisymmetric component is responsible for adjusting the properties on the front and back surfaces towards the specific requirements of the front or back surface, using a symmetric distribution as a starting point. In order to improve the mechanical properties under asymmetric wear and tear service stresses, the asymmetric quality factor (AFOM) of the asymmetric distribution is defined as the integral over the thickness of the absolute value of the stress in the antisymmetric component and the symmetric component, as shown in the following equation (7):
[0147]
[0148] If the AFOM is greater than about 0.05 (e.g., greater than about 0.07, greater than about 0.1, or greater), the stress distribution is considered to be significantly asymmetric. In addition, a significantly asymmetric distribution that provides a major advantage of improved strength on both the front and back surfaces of the glass (relative to the respective major failure modes on the front and back surfaces) can have an AFOM greater than about 0.2 (e.g., greater than about 0.3, about 0.4, about 0.5, about 0.6, or greater).
[0149] The symmetric component of the stress distribution does not contribute to the torque in equation (3) and does not cause distribution-induced warping. Therefore, the entire warping problem that accompanies the introduction of an asymmetric stress distribution is associated with the antisymmetric component, which is also very large for reaping the benefits of a significant asymmetric distribution. A preferred stress distribution that has a large antisymmetric component but still does not cause significant stress distribution-induced warping can be defined as follows. It is generally unexpected that an asymmetric stress distribution with a large antisymmetric component does not produce significant stress distribution-induced warping, because the antisymmetric component is fully responsible for the occurrence of warping.
[0150] The bending moment of the symmetric component of the distribution is zero because it is equivalent to the integral of the antisymmetric function (xσ(x)) in the symmetric interval. Therefore, the two-dimensional bending moment per unit width of the glass article is entirely due to the antisymmetric component of the distribution, as shown in equation (8) below:
[0151]
[0152] For a glass article to be perfectly flat, the bending moment of the antisymmetric component is 0, which requires that the antisymmetric distribution component has regions of both compressive and tensile stress in each half of the sample. Therefore, in one embodiment, the stress distribution has an antisymmetric component that has regions of both compressive and tensile stress in each half of the thickness.
[0153] In pure bending in a two-dimensional model (bending in only one dimension is allowed), the bending moment (M) produces the radius of curvature (ρ) as shown in equation (9):
[0154]
[0155] Where E is the Young's modulus of the glass product (in Pascals), A is the cross-sectional area of the product when it is bent (in m 2 ), and I is the moment of inertia (its unit can be m 4 ), so the unit of the radius of curvature is meters.
[0156] In the case of two-dimensional bending of a glazing article in sheet form (of width (w) and thickness (t) as shown), equation (9) is evaluated to yield the moment of inertia (I) as shown below in equation (10):
[0157]
[0158] Therefore, the relationship between the radius of curvature (ρ) and the bending moment (M) is as shown in equation (11):
[0159]
[0160] It is desirable that a glass product in sheet form having a length (L) of 100 mm has a warp height (H) measured over the length (L) of no more than 0.1 mm and has a radius of curvature of no less than 12.5 m, as further shown in the following equation (12):
[0161]
[0162] In some embodiments, L can be selected as the largest dimension of the glass article. In other embodiments, L can be selected as the dimension along the edge of the glass article.
[0163] In practice, the warping of the glass article may have a complex shape rather than a simple spherical or cylindrical shape, and a significantly smaller radius of curvature may be acceptable locally. Therefore, the maximum acceptable radius of curvature induced by the asymmetric stress distribution may be equal to 1 m (1000 mm). In some embodiments, the glass article may have a peripheral area within 3 mm of the edge that decreases monotonically toward the edge, which may be referred to as a 2.5D shape. In some embodiments, for example, when the edge shape is asymmetric relative to the mid-plane of the glass sheet, the presence of such a 2.5D edge may produce non-negligible warping, which is induced by the interaction of the asymmetric edge shape with the stress distribution. The principal component of the warping induced by such a distribution may be selected to partially or substantially eliminate the warping introduced by the use of an asymmetric stress distribution inside the glass sheet. In such embodiments, an asymmetric distribution of bending moments (M) corresponding to a smaller radius of curvature of even 0.5 m may be acceptable.
[0164] In practice, some glass articles may be designed to have curvature, and a simple measurement of the radius of curvature of the glass article may not represent the curvature introduced by the asymmetric stress distribution. The curvature due to the introduction of the asymmetric stress distribution can be added to the curvature present in the glass article before the introduction of the stress distribution. For glass articles that are substantially free of warp after the introduction of the stress distribution, the curvature present in the glass article before the introduction of the stress distribution is inversely proportional to the radius of curvature (κ), and the following equation (13) provides the inverse of the radius of curvature that can be eliminated by the radius of curvature induced by the stress distribution:
[0165]
[0166] With a maximum length of 2m -1 The asymmetric stress distribution corresponding to the curvature is advantageous, especially when a glass product with a 2.5D or 3D shape is used. In addition, for ease of assembly and higher process yield, it is preferred that the curvature induced by the stress distribution does not exceed 1m -1 , for example, no more than 0.5m -1 Or not more than 0.1m -1 .
[0167] The two-dimensional bending model enables the correlation of the range of curvatures induced by these preferred stress distributions with the appropriate range of bending moments for the stress distributions. It is possible that the actual warp of the sheet may exceed the warp calculated by the schematic two-dimensional model of bending in only one dimension, for example, when the stresses in the glass article exist in two dimensions in the plane of the sheet. However, the illustrated model enables the definition of the preferred stress distribution parameter ranges in a relatively simplified manner.
[0168] Based on equation (11), for a glass article in sheet form, the bending moment resulting from the radius of curvature (ρ) is given by equation (14):
[0169]
[0170] Therefore, the bending moment per unit width resulting from the radius of curvature (ρ) or the inverse of the radius of curvature (κ) is shown in the following equation (15):
[0171]
[0172] In addition, the warpage figure of merit (WFOM) is defined as being maximized when the warpage is minimized. For simplicity, the WFOM is defined with reference to a two-dimensional bending model. The WFOM of the bending moment for an asymmetric stress distribution is related to the radius of curvature (ρ) produced by the asymmetric stress distribution. asym ), which induces a bending moment per unit width in one-dimensional bending of a glass article in sheet form, as shown in the following equation (16):
[0173]
[0174] In some embodiments, WFOM is greater than about 0.5 m, such as greater than about 1 m, about 2 m, about 10 m, or greater. In some embodiments, the change in radius of curvature induced by stress distribution can be used as a direct estimate of WFOM.
[0175] By further solving equation (16), the bending moment per unit width can be defined as follows in equation (17):
[0176]
[0177] When WFOM is infinite, edge effects are neglected and warpage induced by stress distribution is ideally avoided.
[0178] Therefore, the ideal state that minimizes the warpage would be when the following equation (18) is satisfied.
[0179]
[0180] In other words, the antisymmetric components of the stress distribution are moment-balanced on either side of the midplane. In order to minimize warping and operational complexity, an asymmetric distribution with substantially internally balanced antisymmetric components as described in equation (19) below is advantageous:
[0181]
[0182] Wherein, WSF is a warpage suppression factor. In some embodiments, WSF is less than about 0.3, such as less than about 0.2, about 0.1, about 0.05, or less.
[0183] Recognizing that thicker glass articles require greater moments to produce warping, equation (17) can be used to define a preferred range of asymmetric stress distributions that produce similar low levels of warping for different thicknesses. The following equation (20) defines the dimensionless warping tendency (WT) that is independent of thickness:
[0184]
[0185] In some embodiments, WT is less than about t / 12, wherein the thickness (t) of the glass article is in meters. In some embodiments, WT is less than about t / 24, such as less than about t / 48, about t / 240, or less.
[0186] To further elaborate on the concepts mentioned above, Figure 3 An exemplary asymmetric stress distribution is shown. Figure 3 In the example shown, the glass article is 0.5 mm thick, but the distribution can be scaled horizontally to any thickness. The stress distribution can also be scaled vertically to any stress as long as the entire distribution is multiplied by a non-zero constant. Figure 3 A clear illustration of the decomposition of the asymmetric stress distribution 200 into a symmetric component 210 and an antisymmetric component 220 is also provided. The asymmetric stress distribution 200 has a distinct front depth of compression (DOC f = 120 microns) and depth of back compression (DOC b =37 μm), compared with the front side compressive stress (CS f =114MPa) significantly higher back compressive strength (CS b =874MPa). The glass product with asymmetric stress distribution of 200 has no stress distribution-induced warpage, and WFOM is close to infinity. Depth of front potassium layer (DOL f = 200m, 40% of t) is the depth of the back potassium layer (DOL b =40um, five times of 8% t). Figure 3 The AFOM of the asymmetric stress distribution 200 is 0.64, and the WFOM is substantially infinite (e.g., about 10 17 m).
[0187] The asymmetric stress distribution 200 can be obtained by exchanging Na with K ions in an alkali aluminosilicate glass that includes Na2O and is substantially free of K2O in the base glass composition. The front surface can be exchanged at high temperature (450-460°C) in a bath having NaNO3 and KNO3, wherein the concentration of NaNO3 exceeds the concentration of KNO3. For example, the bath can contain about 80% by weight NaNO3 and about 20% by weight KNO3. In one embodiment, the front surface can be ion exchanged by spraying KNO3 onto the front surface of the glass and then maintaining a temperature greater than 440°C for a long time (10-48 hours) without KNO3 on the back side. In another embodiment, during the ion exchange of the front surface, an alkali-free coating that is resistant to alkali penetration is used to block the back surface from ion exchange, for example, spin-on glass or sputtered SiO2. After ion exchange of the front surface, the back surface was ion exchanged in pure KNO3 at 420°C for about 2 hours to achieve a potassium DOL of about 40 um (measured by FSM-6000) without significant ion exchange on the front side. To prevent significant ion exchange of the front surface, the front surface can be partially or substantially completely blocked, for example, with a barrier layer that is very thin or has a small amount of alkali to allow limited alkali flux through the coating. In one embodiment, the barrier layer can be a spin-on glass with less than about 2 mol% alkaline oxides (e.g., less than about 1.5 mol% alkaline oxides). During this second step, the distribution on the front side changes only slightly because of the lower temperature and shorter time.
[0188] like Figure 3 As shown, the compression depth on the front surface is very high, about 24% of the thickness. This deep compression depth on the front surface is an advantageous asymmetric stress distribution. The asymmetric stress distribution has a narrower tensile zone and a limited central tension, which makes the glass article not brittle. Another advantage of the asymmetric stress distribution 200 is that the stress at a depth of 10um from the back surface is very high (over 600MPa), and the stress at a depth of 5um from the back surface exceeds 700MPa. In comparison, the stress of the symmetrical double ion exchange (DIOX) stress distribution in the previously existing glass article is less than 450MPa at 5um, or less than 350MPa. Another advantage of the asymmetric stress distribution 200 is the obvious compressive stress level (66MPa) at a large depth (50um, 10% of t) from the front surface, and the obvious compressive stress level (43MPa) at an even greater depth (75um, 5% of t).
[0189] like Figure 4Shown is a second exemplary asymmetric stress profile 300. The asymmetric stress profile includes a deep compressive stress layer extending between the bottom of the surface compressive peak on the front surface and a certain depth of compression (DOC), and a back surface stress profile that is characteristic of a single-step ion exchange profile. The asymmetric stress profile 300 is selected through numerical simulations of multi-step ion exchange and is selected to produce a force balance.
[0190] In a 0.5 mm thick glass article, an asymmetric stress profile 300 was obtained by deep K ion exchange of the front surface, subsequent heat treatment, followed by a K-concentrated back surface ion exchange, and then a short K-concentrated ion exchange of both surfaces to produce a compressive stress spike. The front surface was ion exchanged at 450°C for about 12 hours in a bath with 38±3 wt% NaNO3 and the remainder KNO3, resulting in a surface compressive stress of about 300 MPa and a FSM-recorded DOL of about 125 um. The sample was then heat treated at 450°C for about 4 hours, resulting in a semi-bell-shaped profile on the front surface, with a drop of about 150-170 MPa in the front surface CS. In the next step, the back surface was ion exchanged at 420°C for about 2 hours in a bath containing 99-100 wt% KNO3 and 0-1 wt% NaNO3. At the same time, additional diffusion occurred on the front surface due to the associated thermal cycle, further reducing the front surface CS to about 140 MPa. Finally, the entire glass article is immersed in a bath containing 0-1 wt% NaNO3 and 99-100 wt% KNO3 at 390°C for about 3-6 minutes to form a shallow compressive stress spike on the front surface, while a small increase in the back surface DOL is produced. In some embodiments, a deeper front spike can also be produced, for example, using a longer spike time and also increasing the duration of the heat treatment step after the initial front surface ion exchange to help flatness when a deeper compressive stress spike is used.
[0191] Figure 4 Also shown is a symmetrical stress distribution 330. The symmetrical stress distribution 330 is obtained by subjecting the entire glass article (both the front and back surfaces) to the same ion exchange and heat treatment steps as the front surface of the asymmetrical distribution. Figure 4As shown, the back surface and edges of the sample with an asymmetric distribution are protected with a layer having a high surface compressive stress of about 830 MPa, a FSM recorded DOL of about 47 um, and a back surface DOC of 41.8 um. Despite the high CS, the rate of decrease of compressive stress with depth on the back surface is low (29 MPa / um), achieving compressive stress greater than about 650 MPa at a depth of 5 um and greater than about 500 MPa at a depth of 10 um. This high level of compressive stress below the back surface makes the back surface and edges of the glass article very secure against fragmentation induced by shallower defects (e.g., those less than about 10 um deep). Compared to the glass article with symmetrical distribution 300, this feature of asymmetric 300 makes the glass article better protected from overstress failure. The front DOC of the front surface of the asymmetric stress distribution 300 is 4% higher than that of the symmetrical stress distribution 330, and the compressive stress is about 8 MPa higher than the entire compression zone. This represents a 6% increase in compressive stress at the depth of the base of the front surface spike (at about 10 um), with progressively higher percentage increases in compressive stress at greater depths up to the front surface DOC.
[0192] The symmetric component 310 and the antisymmetric component 320 of the moment-balanced asymmetric stress distribution 300 are as follows: Figure 5 As shown. The AFOM of the asymmetric stress distribution 300 calculated from equation (7) is 0.41. In this specific numerical example, the bending moment M per unit width is calculated uw Yes -3.35e -4 mm 2 MPa, Young's modulus is 68 GPa (68000 MPa), and WFOM is obtained from equation (16):
[0193]
[0194] The asymmetric stress distribution 300 has a dimensionless warping tendency:
[0195]
[0196] With the help of digital simulation Figure 6An asymmetric stress distribution 400 is illustrated in FIG. The asymmetric stress distribution includes an additional auxiliary antisymmetric component that provides a separate contribution to the AFOM. The auxiliary antisymmetric component is achieved by imparting a warp to the glass sheet shape prior to the ion exchange process, wherein the imparted warp is measured relative to the final desired shape of the glass article. For example, if the final desired sheet shape is substantially flat (e.g., a radius of curvature exceeding several meters, ideally exceeding ten or fifteen meters), then the auxiliary antisymmetric component is obtained by warping the sample prior to ion exchange in a manner that produces an antisymmetric component, and when the glass article is constrained to be a flat glass article, the first moment of the antisymmetric component as described in equation (8) is the same magnitude and opposite sign as the first moment of the antisymmetric component of the ion exchange induced stress. Similarly, if an asymmetric distribution is provided due to a separate ion exchange and the shape is allowed to change, the imparted pre-ion exchange warp is opposite in sign and approximately equal in magnitude to the warp that the part will obtain.
[0197] The auxiliary antisymmetric component of the stress distribution is obtained by heat treatment at a temperature above 500°C (e.g., 560°C for 5 hours) in a mold with a spherical curvature so that the surface of the product has a concave curvature, thereby giving the glass product a spherical curvature. The front surface with a stress distribution is obtained using deep ion exchange (potassium DOL = 125um, measured by FSM-6000), followed by heat treatment, a second heat treatment simultaneously with a high concentration ion exchange of the back surface, and then a double-sided concentrated ion exchange to form a 6μm deep peak on the front surface. The back surface stress distribution has a total potassium DOL of 30um (measured by FSM-DOL) and a high surface CS of 847MPa. The following is performed to obtain a symmetric stress distribution 430: using double-sided ion exchange under the same conditions as the front surface of the sample with asymmetric stress distribution, and then performing the same heat treatment of the total diffusion and the two heat treatments of the front surface of the sample with asymmetric stress distribution, and finally having the same peak of 6μm DOL. Compared to the symmetric stress distribution 430, the asymmetric stress distribution 400 has a substantially deeper high compression (>400 MPa) region on the back surface, a substantially higher front surface compression depth (increased by 13 μm or 13%), and a higher compressive stress in the front surface compression region between the compressive stress peak and the DOC (increased by 19 MPa or >14%). Due to this increase, the inflection point compressive stress (CSk) at the bottom of the compressive stress peak on the front surface increases from about 131 MPa for the symmetric stress distribution 430 to about 150 MPa for the asymmetric stress distribution 400.
[0198] Figure 7The evolution of the normalized concentration profile of the front surface during the ion exchange process is illustrated. Note that in this example, the concentration is normalized so that when the part is constrained to a flat geometry after ion exchange, the ion exchange induced stress is 1,000 MPa when the normalized concentration is 1, and the stress is assumed to be proportional to the local value of the normalized concentration. The concentration profile is not limited to any specific interdiffusible ion pair. In one embodiment, the concentration profile can be obtained by exchanging sodium ions in the glass with potassium ions. Figure 7 As shown, after the front surface ion exchange step, the front surface stress distribution 402 extends from the front surface at C = 0.403 and the FSM DOL is 125 μm. After the combined heat treatment step, the front surface stress distribution 404 extends from the front surface at C = 0.235, and Figure 7 Also shown is the stress profile after application of the double-sided compressive stress spike 406. The concentration profile formed on the back side is not shown.
[0199] Figure 4 The asymmetric distribution 400 and the auxiliary antisymmetric component obtained by pre-warping the sample 440 are shown in Figure 8 . Fig. 9 The symmetric component 410 and the antisymmetric component 420 of the asymmetric distribution 400 are illustrated. The above-described asymmetric distribution 400 may be achieved for the glass composition described in Example 1 below. Figure 3-9 Example stress distribution of .
[0200] The warp height of a glass article can be measured by a profilometer or a flatmaster system. The warp height is the height of the glass article extending from a flat plane, which is measured along the largest dimension of the glass article. For example, the largest dimension of a square article can be a diagonal line extending along a major surface of the glass article between two corners of the glass article. In some embodiments, the warp height of the glass article is less than 1% of the largest dimension of the glass article, such as less than 0.1% of the largest dimension of the glass article.
[0201] In some embodiments, the ratio of the front surface compression depth to the back surface compression depth of the glass article can be at least about 1.5:1, such as at least about 2:1, about 2.5:1, about 3:1, about 3.2:1, or more. In some embodiments, the front surface potassium layer depth to the back surface potassium layer depth of the glass article can be at least about 3:1, such as at least about 3.5:1, about 4:1, about 4.5:1, about 5:1, or more. In some embodiments, the ratio of the front surface maximum compressive stress to the back surface maximum compressive stress of the glass article can be less than about 1:3, such as less than about 1:4, about 1:5, about 1:6, about 1:7, or less.
[0202] In another embodiment, the auxiliary antisymmetric component is provided by providing a coating on the glass article. The coating can be a hard coating with a high modulus, such as aluminum oxynitride (AlON). The coating can be applied to the front (outer) surface of the glass article after the ion exchange is completed. Before applying the coating, the stress distribution of the glass article can be similar to Figure 4 The asymmetric stress distribution 300 shown, but with a larger DOL and / or CS on the back surface, or a smaller CS and / or DOC on the front surface, so that the glass article obtains a concave warp on the surface with higher DOC. The deposition conditions of the coating are then selected so that the film is formed in a compressive state. In one embodiment, the coating thickness can be about 2um and the film compressive stress can be between about 100MPa and about 2,000MPa. The application of the coating causes the stress distribution of the ion-exchanged glass article to have an additional small symmetric component as well as an auxiliary anti-symmetric component. Compared to the warp before the application of the hard coating, the auxiliary anti-symmetric component imparted by the coating will combine with the anti-symmetric component of the ion exchange induced stress distribution to reduce the warp of the glass article.
[0203] In some embodiments, a corresponding stress profile is obtained in a glass article by an initial symmetric ion exchange by immersing a sodium-containing glass in a bath containing a mixture of NaNO3 and KNO3, wherein Na on the surface of the glass article is at least partially replaced by K. In one embodiment, about 40% of the Na in the outermost 2 μm of the glass article is replaced by K. An optional heat treatment step may then be performed, preferably between about 300°C and about 500°C, to increase the depth of the K2O distribution in the glass and thereby increase the DOC. In one embodiment, the glass article is then ion exchanged for a relatively short time in a bath having a majority of KNO3 and typically less than about 5 wt% NaNO3, thereby producing a surface spike in K2O concentration such that more than 80% of the Na in the outermost 2 μm is replaced by K. The depth of the spike may preferably be in the range of about 5-25 μm, at which depth the compressive stress is substantially higher than the compressive stress before the spike was added. In a subsequent step, a portion of the spike on the front surface is removed, for example by polishing or etching, while the spike on the back (inner) surface of the glass article is intact or substantially less polished. The resulting stress distribution is asymmetric and causes the substrate to warp in a direction where the front surface becomes concave. A coating (eg, AlON) is then deposited on the outer surface under conditions that place the coating in compression, causing the coated glass article to flatten.
[0204] In another embodiment, a coated glass article is formed wherein the back surface of the article is ion exchanged to form a spike after a first symmetrical ion exchange and optional heat treatment. To form the spike, a KNO3 coating may be applied by spraying an aqueous KNO3 solution onto a preheated glass article, followed by ion exchange by heating the glass article to a temperature preferably above about 300°C or above about 360°C for a period of about 3 minutes to 10 hours. Preferably, the desired peak depth on the back surface is in the range of about 3 μm to about 25 μm. A shallower peak is then formed on the front surface, either by using the same coating process as for the back surface peak, or by a short double-sided ion exchange in a bath of mostly or all KNO3. The depth of the front surface peak may be in the range of about 3 μm to 15 μm, while the back surface peak has a deeper depth. This asymmetry in stress distribution will cause the glass article to warp, causing the front surface to become concave. The coating is then applied to the front surface using conditions that place the coating in compression, and the coated cover glass becomes substantially flat.
[0205] In some embodiments, the stress distribution of the front and back surfaces of the glass article comprises a deep medium compressive stress portion and a relatively shallow high compressive stress portion. The concentration distribution can be sufficiently approximated as a linear superposition of the solution of the diffusion equation based on the error function (erfc), the diffusion diffuses inward from the two surfaces, and each surface has a characteristic deep diffusion length of the deep distribution portion and a shallow (peak) diffusion length of the shallow portion. This type of distribution can be obtained in sodium-containing glass by using separate steps for the deep portion and the shallow (peak) portion. The deep portion can be obtained by utilizing a long ion exchange time (about several hours) and / or a high ion exchange temperature above 400°C. The peak can be obtained using a short ion exchange time (about a few minutes to a few hours), and a lower ion exchange temperature between about 300°C and about 400°C. These types of distributions can also be obtained in glasses containing Li or containing Li and Na, wherein the deep component of the distribution is obtained by exchanging Li ions with Na ions or Ag ions or Na ions and Ag ions, and the peak is obtained by exchanging any one of Li, Na or Ag with K.
[0206] In one exemplary method for Li-containing glass, the back surface is first subjected to KNO3 coating and heat treatment to form a K-rich peak with a depth of several microns up to about 20 μm. The substrate is then cleaned and ion exchanged in a bath containing KNO3 and NaNO3, which forms a deep component of the distribution by exchanging Na for Li, and shallow peaks of K on both the front and back surfaces, wherein the peak on the front surface is shallower than the peak on the back surface due to the K peak previously formed on the back surface. At the same time, it can be stipulated that although the deep Na distributions exchanged from the two surfaces have the same diffusion length, they do not have the same concentration and the same stress level at depths exceeding the corresponding peak depths. The asymmetry of the deep component of the distribution and the asymmetry of the peak can be selected together to increase the AFOM of the stress distribution but not to reduce the WFOM.
[0207] Considering the deep component and the peak component of the stress distribution, equation (8) can produce the following equation (21):
[0208]
[0209] Where t is the thickness, z 深处 is the diffusion length of the deep distribution (assumed to be equal on both sides in this example), is the contribution of the back surface depth component to the back surface stress, is the contribution of the front surface depth component to the front surface stress, E is the Young's modulus of the glass product, ΔCS 尖峰 is the contribution of the spike to the surface compressive stress (in this example it is assumed that this contribution is equal for the front and back surfaces), and and are the diffusion lengths of the spikes on the back and front surfaces, respectively.
[0210] Based on equation (21), WFOM is then given by the following equation (22):
[0211]
[0212] When measuring and processing erfc-shaped spikes using the FSM-6000 machine, the stress measurement software assumes that the spikes are linearly distributed. In this case, when calculating the corresponding spike "depth of layer" or DOL 尖峰 When only the optical modes confined within the peak (sparse modes) are included, DOL 尖峰 Roughly equal to 1.38z 尖峰 . Therefore, on the front surface of the glass article, And on the back surface,
[0213] Alternatively, to obtain a simpler expression that helps to get a clearer picture of how the warping is related to the parameters of this dual-feature asymmetric peaked curve, a slightly rougher approximation can be used, typically accurate to within 2% to 3%, which is appropriate when the model is only an approximation (the actual distribution is rarely exactly erfc-shaped). 深处 <0.6t, the relationship Established, therefore can be replaced by 1. When z 深处 <0.5t, the relationship Established so that can be replaced by 1. It should be noted that when z 深处 = 0.5t, the front and back surfaces each contribute 0.157 surface concentration to the center, resulting in a center concentration equal to a surface concentration of 0.31. (for 400um thick glass products), and for 800um thick glass products, Therefore, in comparison The corresponding terms can be ignored when the term is used, or can simply be assigned an average value of 0.022 to round the entire expression in the last bracket to 1.15. A simpler expression is then obtained and is described by the following equation (23):
[0214]
[0215] When selecting the preferred conditions When (in this case the center concentration will become 15.5% of the surface concentration, with a contribution of 7.7% from each side), the following equation (24) is obtained:
[0216]
[0217] In addition, if the spike is measured according to the DOL of the FSM 尖峰 When expressing, use the relationship DOL 尖峰 =1.3824*z sp , the following equation (25) is obtained:
[0218]
[0219] in
[0220] One way to avoid warping is to require the value of the expression in the braces to be close to 0. For example, the following equation (26) is required:
[0221]
[0222] This equation will ensure that the asymmetric effect of the auxiliary depth distribution is reduced by at least a factor of 10 due to the offsetting effect of the asymmetry of the peak. Evaluating the above expression yields the following equation (27):
[0223]
[0224] Where the curvature is not strictly constrained, a less strict relationship given by the following equation (28) can be used:
[0225]
[0226] Then evaluate it to get the following equation (29):
[0227]
[0228] In most cases, a moderate limit given by the following equation (30) is appropriate:
[0229]
[0230] The asymmetric nature of the stress distribution described herein can also be characterized based on the concentration distribution of ions in the substrate rather than based on the concentration in the glass article, where stress relaxation during or after ion exchange can be neglected or reduced. The concentration distribution C0(x) as a position (x) in the glass article is given by the following equation (31):
[0231] C0(x)=C(x)-min(C(x))
[0232] In the case of exchanging K for Na in a Li-free glass, only the K concentration needs to be considered. In this sense, a zero-shifted K concentration distribution C0(x) can be obtained relative to the minimum concentration of K across the thickness, which can then be decomposed into symmetric components (C ) given by the following equation (32): s (x)):
[0233]
[0234] With c, the antisymmetric component (C a (x)):
[0235]
[0236] By replacing σ in the above AFOM definition of stress distribution with the symmetric and antisymmetric components of the concentration distribution s and σ a, the same AFOM as described above for stress distribution can be used for the AFOM definition for concentration distribution. Note that the symmetric and antisymmetric components of the zero-biased concentration distribution do not need to be non-negative throughout the thickness, although the zero-biased distribution C0(x) can be non-negative at each point x. The AFOM for concentration distribution is then given by the following equation (34):
[0237]
[0238] The same definitions for the concentration profile at zero offset and the symmetric and antisymmetric concentration components can be used for Li-containing glasses by defining the concentration at zero offset according to the following equation (35):
[0239] C0(x)=C Na (x)-min(C Na (x))+2C K (x)-2min(C K (x)
[0240] Among them, C Na (x) and C K (x) refers to the concentration distribution of Na and K as a function of position, respectively.
[0241] C with potassium K The factor of 2 multiplied by the (x) term reflects that replacing Li ions with potassium ions in a Li-containing glass produces about twice as much stress when replacing Li ions with Na ions. Thus, the glass articles described herein can include a concentration profile with a zero offset having an AFOM greater than 0.05, such as greater than 0.07, 0.1, 0.2, or more. Concentration profiles that can substantially and beneficially better address reliability issues on both the front and back sides of the glass article can have an AFOM in excess of 0.3 or even 0.4.
[0242] The method for measuring the stress distribution of glass products can be different based on the composition of glass products. In some embodiments, stress is obtained in a glass without Li by exchanging sodium with potassium, and when potassium ion concentration is a uniaxial decreasing function of the depth on both sides of the glass substrate, the preferred method for deriving stress distribution is the IWKB derivation method. Since the further reduction of K concentration with depth can be ignored, therefore, the IWKB method derives the distribution to the depth at which the distribution actually stops changing. Then the deepest part of the distribution derived from both sides of the substrate can be connected with a straight line of constant stress, and the stress level of the constant stress line can be finely adjusted so that the stress integral in the tensile zone is equal to the stress integral in the front compression zone and the back compression zone. Afterwards, the complete distribution is fully repaired and balanced, and the calculation of AFOM and WFOM is relatively accurate. It is important to extract the coupled spectrum (FSM spectrum) of TM and TE waves without substantial offset (such as caused by the interference fringes of the polarizer of the instrument or the tilt of the wedge), to avoid the substantial error in AFOM and WFOM.
[0243] In general, when stress relaxation is relatively low, the stress profile obtained by exchanging K for Na in a Li-free glass is directly related to the K concentration profile, and the techniques used to obtain the symmetric and antisymmetric components of the stress profile can be directly applied to the K profile. The lowest K concentration through the thickness can be first subtracted from the entire K profile, and the remaining K profile then has a minimum concentration of 0. It can then be decomposed into symmetric and antisymmetric components, and the AFOM can be calculated in the same manner, where the absolute values of the antisymmetric and symmetric components of the K concentration profile are integrated instead of integrating the antisymmetric and symmetric stress components, and the ratio of the integrals is taken as the AFOM. Alternatively, it can be assumed that for every 1 mol % of K2O, a stress of 60±10 MPa is generated, with larger values (e.g., 70 MPa / mol %) corresponding to annealed glass, intermediate values (60-65 MPa / mol %) corresponding to fusion sheet glass, and lower values (50-60 MPa / mol %) corresponding to conditions with a moderate and acceptable level of stress relaxation. The K2O concentration distribution that has been moved to a zero minimum is converted into a stress distribution (with a zero minimum), and force balancing can be performed by subtracting constant stress values until the integral of the negative stress is equal to the integral of the positive stress. Finally, the distribution can be decomposed into symmetric and antisymmetric components, and AFOM can be calculated. In addition, using the stress distribution thus obtained, WFOM and warpage tendency can also be calculated.
[0244] The method of AFOM and WFOM using concentration estimation distribution can also be extended to Li-containing glasses strengthened with Na and K, strengthened with Na only, or strengthened with K only. In particular, the K2O distribution and the Na2O distribution can be derived by GDOES (glow discharge optical emission spectroscopy) or EMP (electron microprobe) or other analytical methods in the field. In the case of EMP, where the noise is usually more, the slowly varying part of the concentration distribution should be essentially denoised. The minimum concentration of each distribution is then subtracted from the entire spatial distribution of this particular case to obtain a distribution with a minimum value of 0. However, each 1 mol% of Na2O is replaced by a stress of 60±10 MPa, while each 1 mol% of K2O is replaced by a stress of 120±20 MPa, where the higher values correspond to annealed glasses or glasses with a molar concentration of Li2O twice or more than Na2O in the mid-plane of the glass sheet, and intermediate values are applicable to glasses with similar molar concentrations of Li2O and Na2O in the mid-plane of the substrate or Na2O higher than Li2O. Finally, the lower half of the range is applicable to glasses with moderate levels of stress relaxation. Through this conversion, a stress distribution with a minimum stress of zero is obtained from the sum of the stress components corresponding to the Na2O and K2O distributions. Finally, the distribution can be converted into a force balance and its symmetric and antisymmetric components can be calculated. Note that applying a force balance is not a required step for the purpose of calculating the antisymmetric portion of the distribution (e.g., applying a force balance is optional).
[0245] Derivation of the CS of chemically strengthened Li-containing glasses by using prism coupling measurements k The method can also be used to estimate the properties of asymmetric distributions. Note that in order to accurately estimate CS from prism-coupled spectroscopy of an FSM-6000 or similar instrument k , the wavelength is necessary to put the upper (TM) and lower (TE) spectra in the "sweet spot" to measure the position of the critical angle. In the case of Li-containing glasses strengthened in a mixed bath with Na and K salts, the mode spectra obtained by the prism coupling method only provide surface CS and DOL about the relatively shallow K peak, and the "compressive inflection stress" CS at the base of the K peak. k When the Na profile is deep enough so that the spatially varying portions of the Na profile extending from the two surfaces are connected within the substrate where there is no significant region of constant Na concentration (e.g., any region with constant Na concentration near the mid-plane of the substrate whose width is less than about 20%, preferably less than about 15% of the substrate thickness), then the surface CS, peak DOL, and CS kThe difference in the measured parameters between the front and back of the cover glass sheet can be used to determine whether the article falls within the range characterized by high AFOM and high WFOM as defined in the present disclosure. In addition, the central tension (CT) can be measured by a scattered light polarimeter (SCALP) and used as needed to verify the consistency between the different parameters of the distribution.
[0246] Refractive near field measurements (RNF) have been successfully used to derive the difference between the front and back sides of an asymmetric distribution (in this disclosure, the 0.5 mm sample M3B from the examples, which utilizes an auxiliary antisymmetric component). In order to determine if the distribution is asymmetric, the sample needs to be scanned starting from one side and then again starting from the other side, and both scans should be interrupted at the depth of the midplane of the substrate. They are then moved vertically to a common stress value at the junction point (midplane). If necessary, a force balance can be applied at this point. The symmetric and antisymmetric components of the spliced complete distribution can be calculated by the equations provided, and AFOM and WFOM can be calculated.
[0247] exist Fig.32 In the present invention, an asymmetric distribution was obtained by pre-warping a 0.5 mm substrate at 570°C for 3 hours to produce a concave warp on the front side of the sheet with a radius of curvature of approximately 1,500 mm. The back side was then ion exchanged at 390°C for 60 minutes in a shallow bath with 1 wt% LiNO3 and 99 wt% KNO3, followed by a full immersion ion exchange at 380°C for 1.25 hours in a bath with 49 wt% NaNO3 and 51 wt% KNO3, and finally a full immersion ion exchange at 380°C for 20 minutes in a bath with 4 wt% NaNO3 and 96 wt% KNO3. The RNF distribution obtained using the above procedure shows the front side inflection point stress Back inflection stress 18±2MPa, and the compression depth of the front side (DOC f ) is deeper than the dorsal compression depth (DOC b ) about 6-7 microns. Prism coupling stress measurements after the first IOX step on the backside reported a surface CS of about 860 MPa and a DOL of 6.4 microns. After the second ion exchange step, the backside CS was about 530 MPa and the DOL was 10.5 microns. Finally, after the third IOX step, the backside read CS = 815 MPa and the DOL was 10.5 microns. b = 10.65 μm, while the reading on the front side is CS f =838MPa and DOL f=7.8 μm. Note that the CS value is slightly underestimated by the conventional FSM-6000 measurement, which is not optimally designed for measuring steep stress spikes shallower than 20 microns. In this case, the actual value of the surface CS is closer to 950 MPa. In the case of such shallow spikes, a more accurate measurement of the surface CS uses the linear spike approximation, where the surface index at each polarization is calculated by adding the index of the lowest order mode to 1.3 times the difference between the lowest order mode and the next mode. In the FSM-6000, only a difference of 0.9 is added, which generally underestimates the surface index for shallow spikes.
[0248] The RNF distribution does not provide an accurate surface CS measurement due to limited resolution, so parameters such as CS and DOL of the front and back K-spikes are more accurately measured by FSM.
[0249] Another stress measurement method that can be used to evaluate stress distribution is DOC measurement by using a polarization microscope. This can be used to try to measure the difference between the front side DOC and the back side DOC on the sample.
[0250] In the case of an asymmetric stress profile using a majority of the auxiliary antisymmetric components obtained by pre-warping the glass sheet (e.g., pre-warped radius of curvature < 1,000 mm), the calculation of the WFOM from the concentration profile may not match the final inverse radius of curvature of the glass sheet as closely as it should. In this case, the inverse radius of curvature of the sheet can be used as a direct estimate of the WFOM, while the AFOM can still be estimated from the stress profile measured optically or from the stress profile obtained by converting the measured concentration profile to stress.
[0251] It has been shown that a distribution of surface peaks with high CS (e.g., >650 MPa) can help improve the scratch resistance of the glass. f), many embodiments of the present disclosure attempt to have a substantially shallow stress peak on the front side, or no peak at all on the front surface. In some embodiments, such an asymmetric distribution can be used for glass articles having a substantial concentration of B2O3 preferably exceeding 1 mol%, 1.5 mol%, or 2 mol%, and preferably not exceeding 40 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, or 7 mol%. For this recommendation of B2O3 content, the following asymmetric distributions are particularly recommended: an asymmetric distribution with no peak on the front surface, or an asymmetric distribution with a peak on the front side that is shallower than the peak on the back side, or an asymmetric distribution with a CS on the front surface at least 50 MPa lower than the CS on the back surface, or an asymmetric distribution with a front surface CS below 600 MPa. Similarly, it is recommended that glass articles comprising an asymmetric distribution having the above-mentioned CS properties contain at least 1 mol%, 1.5 mol% or 2 mol% P2O5, and preferably no more than 15 mol%, 10 mol% or 7 mol% P2O5.
[0252] In another embodiment of the invention, a final polish can be applied to one of the two surfaces of an ion-exchanged glass article having an asymmetric stress distribution to remove cosmetic defects or to eliminate any undesirable residual warpage relative to the target final shape, such as variable residual warpage caused by fluctuations in heating or cooling conditions, fluctuations in salt concentration during ion exchange, or fluctuations in the uniformity of the K and Na ion coating sources. As a result, the CS on the front surface can differ by 30 MPa or more from the CS on the back surface, even though the final ion exchange step produces substantially the same surface compression on the front and back surfaces before the final cosmetic polish.
[0253] In another embodiment of the present invention, the front surface inflection stress of the glass article of the present invention is Back inflection stress The CS between the front and back surfaces of the glass article is greater than 4 MPa, preferably greater than 6 MPa, and ideally greater than 8 MPa, and the article is substantially flat (radius of curvature greater than 500 mm). The above-described 0.5 mm Li-containing glass article with a measured asymmetric experimental distribution is an example of such an inventive glass article. In a specific embodiment, the glass article can be a Li-containing glass, but the same type of asymmetric distribution can also be obtained in a Li-free glass, if the thickness is the same, which is generally achieved by running the ion exchange process for a longer time. When a light cosmetic polish is applied to one or both large surfaces of a glass sheet representing the article, the CS between the front and back surfaces of the glass article is greater than 500 mm. K The change in the difference (usually less than 1 MPa) is negligible, so the CS between the front and back sides of the glass article kThe substantial difference is a relatively robust way to establish the asymmetric nature of glass products and to measure AFOM.
[0254] In some embodiments, the glass articles herein may be formed by down-drawing processes known in the art, such as slot draw and fusion draw. Fusion draw is an industrial technique that has been used to manufacture thin glass sheets on a large scale. Compared to other flat glass manufacturing techniques, such as float or slot draw, thin glass sheets produced by fusion draw have excellent flatness and surface quality. As a result, fusion draw has become a mainstream manufacturing technology for thin glass substrates used in liquid crystal displays and cover glasses for personal electronic devices, such as laptops, entertainment devices, tablets, portable computers, mobile phones, etc.
[0255] The fusion draw process involves flowing molten glass out of a trough called an "isoppe," which is usually made of zircon or another refractory material. The molten glass overflows the top of the isopipe from both sides and joins at the bottom of the isopipe to form a single sheet, where the isopipe is in direct contact only with the interior of the final sheet. Since none of the exposed surfaces of the final glass sheet come into contact with the isopipe material during the drawing process, both exterior surfaces of the glass are of perfect quality without the need for subsequent finishing.
[0256] In order to be able to be fusion drawn, the glass composition must have a sufficiently high liquidus viscosity (i.e., the viscosity of the molten glass at the liquidus temperature). In some embodiments, the liquidus viscosity of the composition used to form the glass articles described herein is at least about 50 kilopoise (kP), such as at least about 100 kP, about 200 kP, about 300 kP, about 400 kP, about 500 kP, about 600 kP, or more.
[0257] In some embodiments, the glass article can be a laminated glass article. The laminated glass article can include at least 2 glass article layers, such as at least 3 layers, 4 layers, 5 layers or more layers. The glass article layers can also be selected to have different thermal expansion coefficients to establish a stress distribution in the laminated glass article. The stress distribution in the laminated glass article by the difference in properties between the glass article layers can be combined with the above-mentioned asymmetric stress distribution. In some other embodiments, the glass article layers can be selected to have different ion diffusion properties so that the same ion exchange conditions produce different ion diffusion degrees in each glass article layer. The laminated glass article can be formed by combining separately formed glass article layers, or by forming each glass article layer simultaneously.
[0258] The glass article can be of any suitable composition. In some embodiments, the glass article is an aluminosilicate glass, such as an alkali aluminosilicate glass. In some embodiments, the glass article contains lithium. In some embodiments, the glass article can include B2O3 in an amount of about 2 mol % to about 20 mol %. The glass article can have a composition comprising: 50-75 mol % SiO2, 5-20 mol % Al2O3, 2-20 mol % B2O3, 0-10 mol % P2O5, 6-25 mol % Li2O+Na2O+K2O, and 0-15 mol % MgO+CaO+SrO+BaO+ZnO.
[0259] After the glass article is formed, the article can be chemically strengthened. Ion exchange is widely used for chemically strengthening glass. In a specific example, the alkali metal cations in the cation source (e.g., molten salt or "ion exchange" bath) are exchanged with smaller alkali metal cations in the glass to obtain a layer under compressive stress near the surface of the glass article. The compression layer extends from the surface to the DOC in the glass article. In the glass article described herein, for example, during ion exchange, potassium ions from the cation source are exchanged with sodium ions in the glass by immersing the glass in a molten salt bath containing potassium salts, such as but not limited to potassium nitrate (KNO3). Other potassium salts that can be used for ion exchange processes include, but are not limited to: potassium chloride (KCl), potassium sulfate (K2SO4), combinations thereof, and the like. The ion exchange bath described herein may contain alkali metal ions other than potassium and corresponding salts. For example, the ion exchange bath may also contain sodium salts, such as sodium nitrate (NaNO3), sodium sulfate, sodium chloride, and the like. In one or more embodiments, a mixture of two different salts may be used. For example, the glass article may be immersed in a salt bath of KNO3 and NaNO3. In some embodiments, more than one bath may be used, with the glass being immersed in one bath first and then sequentially immersed in another bath. Each bath may have the same or different composition, temperature and / or may use different immersion times.
[0260] The temperature of the ion exchange baths described herein may range from about 320° C. to about 520° C., such as about 320° C. to about 450° C. The immersion time in the bath may vary from about 15 minutes to about 48 hours, such as from about 15 minutes to about 16 hours.
[0261] The asymmetric distribution described herein can be produced by any suitable ion exchange process. In some embodiments, the front surface and the back surface can be ion exchanged in separate processes. This can be achieved by contacting only the desired ion exchange surface with a salt containing the ions to be exchanged. In some embodiments, selective contact with the ion exchange salt can include applying a solution or paste containing the ion exchange salt to the desired surface without contacting other surfaces of the glass article. In some other embodiments, a barrier layer can be applied to the surface of the glass article where the ion exchange process is not desired. The barrier layer can completely block ion diffusion, or in some embodiments, partial ion diffusion can be allowed to set the surface on which the barrier layer is located to be ion exchanged to a lower degree than the surface without the barrier layer. Exemplary barrier layers can be spin-on glass or silicon dioxide.
[0262] The barrier layer can be formed of any suitable material by any suitable method. In some embodiments, the barrier layer can be formed of alkali-free spin-on glass (SOG), sputtered SiO2, or an evaporated or sputtered metal coating. In some embodiments, the barrier layer can be a sputtered SiO2 layer. The thickness of the sputtered layer can be about 40nm to about 70nm. In some embodiments, the barrier layer can be a metal coating, such as a coating containing tantalum, molybdenum, or aluminum.
[0263] In some embodiments, the barrier layer can be an alkali-free spin-on glass and can be deposited by spin coating at a speed of 3000 to 6000 rpm and then curing the coated glass at about 400°C for about 1 hour. The thickness of the cured SOG layer can be about 50nm to about 200nm. The SOG layer can be removed after ion exchange by etching in a buffered oxide etch (BOE), such as a BOE containing hydrofluoric acid or ammonium fluoride. At room temperature, the etching can be extended from about 15 seconds to about 3 minutes. The dilute nature of the etchant in the BOE solution facilitates the removal of the SOG barrier layer of the ion-exchanged glass to a minimum extent at the nanometer level. The BOE method can also be used to remove sputtered SiO2 barrier layers.
[0264] In some other embodiments, the barrier layer can be formed by ion exchanging at least one divalent metal ion into the glass article. The divalent metal ion can be at least one of Cu, Ca, Mg, Zn and Ti. In some embodiments, a mixture of more than one divalent cation can be used in the salt, which can increase the effectiveness of the barrier layer to inhibit subsequent ion exchange for a longer period of time. The divalent metal ions can be obtained using nitrates of divalent metal ions [e.g., Cu(NO3)2 or Ca(NO3)2]. The salt can be sprayed onto the surface to be exchanged in the following manner. The ion exchange can be performed by heating the salt-coated substrate at a temperature of about 400°C to about 500°C for a time of about 5 minutes to about 3 hours, for example, at a temperature of about 420°C for about 2 hours. The divalent metal ions can be exchanged to a layer depth of less than about 1 μm. The salt is washed off after the ion exchange. In some embodiments, the barrier layer can be removed by chemical methods or mechanical methods, such as acid washing or mechanical polishing. After removing the barrier layer, the glass article can be subjected to additional ion exchange steps.
[0265] In some embodiments, the glass article may be ion exchanged to form a compressive stress spike on one or both surfaces. In some embodiments where the compressive stress spike is formed on both the front and back surfaces, the spikes may have similar compressive stress values on each surface. In some embodiments, as the compressive stress spike is formed on both surfaces of the glass article, the values of the compressive stress on the front and back surfaces may be substantially different despite being subjected to the same spike ion exchange conditions. This difference in the value of the compressive stress spike may be due, at least in part, to the different ion exchange treatments previously performed on each surface, which alters the ion diffusion of the glass article.
[0266] Ion exchange of the glass article can be combined with one or more heat treatments. Heat treatment can allow ions that have been exchanged into the glass article by a previous ion exchange treatment to further diffuse throughout the glass article, which can increase the depth of compression and the depth of layer of potassium. Heat treatment can also be used to give the glass article a pre-warped shape prior to ion exchange, such as a pre-warped shape imparted by a mold. In some embodiments, the pre-warped glass article is stress-free prior to ion exchange. The degree of pre-warp imparted to the glass article can be selected to offset warping induced by asymmetric stress distribution formed during ion exchange.
[0267] The DOC on either surface of the glass article may be described as a fraction of the thickness t. For example, in one or more embodiments, the DOC on either the front or back surface may be equal to or greater than about 0.1t, equal to or greater than about 0.11t, equal to or greater than about 0.12t, equal to or greater than about 0.13t, equal to or greater than about 0.14t, equal to or greater than about 0.15t, equal to or greater than about 0.16t, equal to or greater than about 0.17t, equal to or greater than about 0.18t, equal to or greater than about 0.19t, equal to or greater than about 0.2t, equal to or greater than about 0.21t. In some embodiments, the DOC on the front or back surface of the glass article may be in the range of about 0.08t to about 0.25t, about 0.09t to about 0.24t, about 0.10t to about 0.23t, about 0.11t to about 0.22t, about 0.12t to about 0.21t, about 0.13t to about 0.20t, about 0.14t to about 0.19t, about 0.15t to about 0.18t, about 0.16t to about 0.19t, or any subranges included therein or formed by any of these endpoints. In some cases, the DOC of the front or back surface may be about 20 μm or less. In one or more embodiments, the DOC of the front or back surface of the glass article may be about 40 μm or higher, for example, about 40 μm to about 300 μm, about 50 μm to about 280 μm, about 60 μm to about 260 μm, about 70 μm to about 240 μm, about 80 μm to about 220 μm, about 90 μm to about 200 μm, about 100 μm to about 190 μm, about 110 μm to about 180 μm, about 120 μm to about 170 μm, about 140 μm to about 160 μm, about 150 μm to about 300 μm, or any subranges included therein or formed by any of these endpoints.
[0268] In one or more embodiments, the strengthened alkali aluminosilicate glass article may have a maximum compressive stress at the front or back surface (which may be found at the surface or at depth in the glass article) that is about 400 MPa or more, about 500 MPa or more, about 600 MPa or more, about 700 MPa or more, about 800 MPa or more, about 900 MPa or more, about 930 MPa or more, about 1,000 MPa or more, or about 1,050 MPa or more.
[0269] In one or more embodiments, the strengthened alkali aluminosilicate glass article may have a maximum tensile stress or central tension (CT) of about 40 MPa or more, such as about 45 MPa or more, about 50 MPa or more, about 60 MPa or more, about 70 MPa or more, about 75 MPa or more, about 80 MPa or more, or about 85 MPa or more. In some embodiments, the maximum tensile stress or central tension (CT) may be in the range of about 40 MPa to about 100 MPa.
[0270] In some embodiments, the glass article may include portions having different stress distributions. For example, a first region of the glass article may include a first stress distribution, and a second region of the glass article may include a second stress distribution, wherein at least one of the first stress distribution and the second stress distribution is an asymmetric stress distribution. The glass article may include a mixture of asymmetric stress distributions and symmetric stress distributions. In some embodiments, the stress distributions in various regions of the glass article may be selected to address common failure modes in glass use. For example, when compared to the central region of a glass article to be used for consumer electronic devices, the corners and / or edges of the glass article may exhibit increased strength, wherein the corners and edges are more susceptible to impact, such as landing on a hard surface. In addition, by including multiple stress distributions in the glass article, a more asymmetric stress distribution may be included in certain regions of the glass article, where the distribution provides increased performance, while a less asymmetric stress distribution is included in other regions, so that the higher asymmetry achieves the benefit of low warping. Warping caused by a localized asymmetric stress distribution can generally be confined to areas exhibiting the asymmetric stress distribution, such that a glass article having a localized asymmetric stress distribution warps less than a glass article having a single asymmetric stress distribution over the entirety of the glass article.
[0271] In some embodiments, the glass article may include a stress distribution having an AFOM difference greater than about 0.2, such as greater than about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, or more. In some embodiments, the AFOM of the asymmetric stress distribution in a localized strengthened region (e.g., a corner or edge of the glass article) may have an AFOM greater than about 0.2, such as greater than about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, or more. The glass article may have an area greater than about 2 cm 2In some embodiments, the glass article may have a region where the radius of curvature due to the stress distribution in the region exceeds about 10 m, and a second region having a WFOM less than about 5 m, such as less than about 3 m, about 1 m, about 0.6 m, about 0.4 m, or less. In addition, the AFOM of the second region may be at least about 0.2, such as at least about 0.3, about 0.4, about 0.5, about 0.6, or more. In general, regions of the glass article can be characterized by any type of stress distribution described herein.
[0272] In some embodiments, the ion-exchanged glass article may contain large ions, such as silver, copper, cesium, or rubidium. The content of these large ions in the ion-exchanged glass article may be up to about 5 mol%, such as up to about 3 mol%.
[0273] In some embodiments, the glass article can be produced by placing a salt containing a solid component on at least a portion of the first surface of the glass article. The glass article is then subjected to ion exchange to produce an asymmetric stress distribution by heating the glass article to an ion exchange temperature. The solid component is selected to be solid at the ion exchange temperature. In some embodiments, the salt may additionally include a liquid component, which is selected to be liquid at the ion exchange temperature.
[0274] The solid component can be a sulfate or a phosphate. In some embodiments, the solid component can be an alkali sulfate or an alkali phosphate, such as tripotassium phosphate (TKP), trisodium phosphate (TSP), potassium sulfate or sodium sulfate. The solid component can include more than one sulfate or phosphate, such as a mixture of phosphates and / or sulfates. The solid component can be present in the salt in an amount of about 5% by weight to about 99.5% by weight, such as about 15% by weight to about 99.5% by weight, about 30% by weight to about 98% by weight, any sub-range included therein. As further described below, the amount of the solid component in the salt can be selected based on the desired effect of the solid component included. In an embodiment where the solid component is present in the salt in an amount of about 30% by weight to about 98% by weight, it is achieved to suppress the distribution of salt during ion exchange, prevent poisoning, and be easy to measure surface stress.
[0275] The liquid component may be a salt in a molten state commonly used in ion exchange processes. In some embodiments, the liquid component may be an alkali metal nitrate, such as KNO or NaNO. The liquid component may contain more than one alkali metal nitrate, such as a mixture of KNO and NaNO. The similar densities of TKP and TSP and KNO and NaNO indicate that any salt mixture containing TKP, TSP, KNO and NaNO may be expected to produce similar results when the weight fractions of the solid and liquid components are similar.
[0276] Even in embodiments where the salt also contains a liquid component, the solid component in the salt prevents the salt from wicking during ion exchange. Preventing wicking allows the salt to be placed on the surface of the glass article in areas where ion exchange is desired and maintains the desired patterning of the salt during the ion exchange process. The reduction in wicking can be at least partially attributed to the attractive force between the surface areas of the liquid component and the solid component of the salt. In contrast, when a salt that does not contain a solid component of the type described herein is used, the salt can wick or diffuse when heated during the ion exchange process, which can cause the salt to migrate to areas of the glass article where ion exchange is not desired. Inhibiting the spreading of the salt can be achieved when the solid content in the salt is from about 15% by weight to about 99.5% by weight.
[0277] In some embodiments, the solid component can also be used as a getter to poison ions that may be exchanged from the glass article. + It is a poisonous ion for Li-containing glass, Na + is a poisoning ion for Na-containing glass. The solid component can then prevent the poisoning ions from participating in the reverse ion exchange process at the surface of the glass article, thereby suppressing the poisoning effect. The suppression of the poisoning effect allows the desired surface concentration of the exchanged ions to be achieved. The suppression of the poisoning effect can be observed when the solid component is present in the salt in an amount of about 5 wt % to about 99.5 wt %.
[0278] The salt can be placed on the first surface by any suitable process. In some embodiments, a solution containing the desired salt can be sprayed onto the glass article. The salt mixture is then dried to remove the solvent, thereby leaving a dry salt coating on the glass article. In some embodiments, the solvent can be water, such as deionized water. In other embodiments, the salt can be deposited by other methods known in the art, such as inkjet printing, screen printing, or roller pressing.
[0279] The salt can be placed on the first surface in a certain pattern so that areas of the first surface are not in contact with the salt. When the glass article is heated to the ion exchange temperature, this allows the generation of areas of the first surface that are not ion exchanged. The resulting glass article can then have areas with different stress distributions. For example, the salt can be deposited at the perimeter of the first surface but not at the center of the first surface, which results in ion exchange at the corners of the first surface while not at the center. This localized ion exchange allows preferential ion exchange in areas of the glass article that are desired to be additionally strengthened, such as corners and edges that are more likely to be impacted during use. In other embodiments, the salt can be placed on the entire first surface of the glass article.
[0280] The salt pattern on the first surface can be produced by any suitable process. In some embodiments, a mask can be used to block areas of the first surface that will not be ion exchanged. The mask can be removed before heating the glass article to the ion exchange temperature. The mask can be formed of any suitable material, such as a polymer, glass, or metal.
[0281] After the glass article is ion exchanged, the salt layer is removed. The salt layer can be removed by any suitable method, such as by washing with a solvent. In some embodiments, the salt is removed by washing the glass article with water. The glass article can also be cleaned with an acid wash to remove contaminants generated by the ion exchange process. In some embodiments, the glass article can be washed with acetic acid to remove contaminants on the first surface of the glass article.
[0282] The cleaned ion exchange glass article can then be subjected to an additional ion exchange process. In some embodiments, the ion exchange can be performed by immersing the cleaned glass article in a molten salt bath of a type commonly used in the art. Both the first and second surfaces can be ion exchanged in an additional ion exchange process. In some embodiments, the cleaned ion exchange article can be subjected to two additional ion exchange processes using different salt bath compositions.
[0283] In some embodiments, a barrier layer may be provided on at least a portion of the glass article prior to depositing the salt. The barrier layer may be formed from any suitable material by any suitable method, such as those described above. In some embodiments, the barrier layer may be formed from alkali-free spin-on glass (SOG), sputtered SiO2, or an evaporated or sputtered metal coating. In some other embodiments, the barrier layer may be formed by ion-exchanging at least one divalent metal ion into the glass article. The divalent metal ion may be at least one of Cu, Ca, Mg, Zn, and Ti. The barrier layer may be removed after ion exchange by any suitable process. In some embodiments, the barrier layer is removed by an acid pickling or mechanical polishing process.
[0284] In some embodiments, a barrier layer may be formed at the first surface of the glass article before the glass article is immersed in the molten salt bath. At a temperature of about 460°C, the molten salt bath may contain about 40% by weight of NaNO3 and about 50% by weight of KNO3. The glass article may be immersed in the molten salt bath for about 14 hours. In some other embodiments, the molten salt bath may contain KNO3 and about 5% by weight to about 60% by weight of NaNO3. In some embodiments, the glass article may be immersed in the molten salt bath for about 6 hours to about 30 hours at a temperature of about 450°C to about 460°C. The depth of the potassium layer produced by the first ion exchange step may be about 60 μm to about 250 μm, or about 200 μm to about 400 μm. After leaving the molten salt bath, the glass article is cleaned and the barrier layer is removed. The non-ion exchange portion of the cleaned and barrier-free glass article may then be subjected to an ion exchange treatment, for example, by coating the ion exchange portion with a barrier layer or by ion exchanging the non-ion exchange portion with a salt containing a solid component of the above type. In some embodiments, the ion-exchanged surface of the glass article may be coated with a barrier layer of the type disclosed above. The ion-exchanged glass article with the barrier layer can then be immersed in a molten salt bath. The molten salt bath mainly contains KNO3, such as a molten salt bath containing less than 5% by weight of NaNO3 or containing no NaNO3. The ion exchange in the molten salt bath can be carried out at any appropriate time and temperature, such as at 420°C for about 2 hours. The resulting compressive stress layer may have a depth of about 40um and a surface compressive stress of about 800MPa to about 900MPa. Due to the heat treatment experienced by immersion in the molten salt bath, immersion in the molten salt bath can also reduce the surface compressive stress in the previously ion-exchanged area of the glass article. After leaving the molten salt bath, the barrier layer can be removed by chemical etching or mechanical polishing. In addition, by immersing the glass article after removing the barrier layer in the molten salt bath, a compressive surface stress "spike" can be applied to the glass article. The "spike" molten salt bath mainly contains KNO3, such as a molten salt bath containing less than 5% by weight of NaNO3 or containing no NaNO3. "Spike" ion exchange may occur at about 390°C for about 10 to about 15 minutes.
[0285] In some embodiments, a salt may be placed on a non-ion exchange surface of a glass article. The salt may comprise a solid component of the type described herein and may be applied by a spray process as described herein. The glass article is then subjected to ion exchange by heating the glass article to an ion exchange temperature. The compressive stress layer formed by the ion exchange may have a depth of about 40 μm to about 50 μm and a surface compressive stress of about 900 MPa. The ion exchange may be performed at an ion exchange temperature of about 420°C for about 2 hours. The salt layer may then be removed from the glass article, for example by washing. In addition, a compressive surface stress "spike" may be applied to the glass article by immersing the glass article after removing the barrier layer in a molten salt bath. The "spike" molten salt bath contains primarily KNO3, such as a molten salt bath containing less than 5 wt% NaNO3 or no NaNO3. The "spike" ion exchange may occur at about 390°C for about 10 to about 15 minutes. After the "spike" treatment, the first side of the glass article may exhibit a K-rich surface. + The glass article is a glass article having a shallow layer of K2O concentration, wherein the K2O concentration decreases from about 14 mol% to about 16 mol% at the surface to 5 mol% over a distance of several microns (e.g., about 6 μm to about 12 μm). The second side of the glass article is the surface that is ion exchanged with the sprayed salt, which exhibits an increase in the depth of the potassium layer. When the glass article has a thickness of about 0.8 mm, the second side may have a potassium layer depth of about 40 μm to about 50 μm. When the thickness of the glass article is smaller, the potassium layer depth of the second side may be smaller to avoid undesirable brittle properties, such as about 30 μm to about 42 μm for a glass article of about 0.5 mm thickness.
[0286] In some embodiments, the use of barrier layer processes and solid salt containing processes described herein may be used together in any combination and in any order to achieve a desired stress profile.
[0287] In some embodiments, the glass articles described herein form part of a consumer electronic product (e.g., a cell phone or smartphone, a laptop computer, a tablet, etc.). A schematic diagram of a consumer electronic product (e.g., a smartphone) is shown in FIG. Fig.10 and 11 . Consumer electronic device 500 includes housing 502 having front surface 504, back surface 506, and side surface 508; electronic components (not shown) at least partially or completely located within the housing and including at least a controller, memory, and display 510 at or adjacent to the front surface of the housing; and a cover substrate 512 at or on a surface of the housing such that the cover glass is on the display. In some embodiments, cover substrate 512 and / or the housing can include any of the glass articles disclosed herein.
[0288] Exemplary Embodiments
[0289] Example 1
[0290] The glass product samples have the following composition: 57.43 mol% SiO2, 16.10 mol% Al2O3, 17.05 mol% Na2O, 2.81 mol% MgO, 0.003 mol% TiO2, 0.07 mol% SnO2 and 6.54 mol% P2O5. The sample is in the form of a 2 inch x 2 inch square plate with a thickness of 0.4 mm, 0.5 mm or 0.8 mm.
[0291] The samples were rinsed with deionized (DI) water and then weighed to high precision specifications. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface could dry quickly and there was no residual water on the resulting salt precipitate. The temperature of the sample was estimated to be between about 80°C and 150°C. The actual number of sprays applied to the sample surface depended on the weight of salt desired on the sample. The number of sprays was 15 to 30. After the spraying was completed, the sample was weighed again to determine the total weight gain of the salt. The total weight of the salt on the sample was between 0.07g and 0.15g, depending on the salt composition used. The sample was then placed in an oven at 460°C with the sprayed side facing up for 8 hours when the sample thickness was 0.4mm; when the sample thickness was 0.5mm or 0.8mm, the sample was placed in an oven at 460°C with the sprayed side facing up for 14 hours. Also, when the samples were placed in the furnace, they were covered with a glass petri dish lid that was not in contact with the sample surface. The coated sample surface was recorded as the "back" surface, which had a negative warp and convex shape. Table 1 below records the conditions used for the first 10X step.
[0292] The total amount of salt used in the spray treatment (by weight) was 58 g dissolved in 200 mL of deionized water. Four different salt solutions were prepared for use in the first 10X step, including: 100% KNO3, 10% NaNO3 / 90% KNO3, 40% NaNO3 / 60% KNO3, and 50% NaNO3 / 50%
[0293] KNO3. Prepare these salt solutions in separate containers and dissolve them before they are pressed into the spray can to remove large particles of contaminants.
[0294] The specimens were characterized after the first 10X step by: rinsing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer; weighing using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection compressive stress, and depth of layer.
[0295] The second step in the 10X treatment is to spray the opposite side of the sample from the first 10X step. This opposite side is recorded as the "front" surface, which has a negative warp and concave shape. The treatment uses about 0.18g to 0.2g of 100% KNO3 salt based on the weight of the salt. In the second 10X step, the surface is coated using a hot plate in the same manner as the first 10X step. Once the sample is coated, it is placed in a furnace at 420°C with the salt side facing up for a total of 1.5 hours to 2 hours and covered again in the same manner as the first 10X step.
[0296] The third IOX step was to spike the stress profile on both sides of the sample with a 99.5% KNO3 / 0.5% NaNO3 solution in a double-sided ion exchange bath. The sample was preheated at 250°C for 5 minutes, followed by 380°C for 5 minutes. The sample was then ion exchanged in a salt bath at 390°C for 8 minutes or 11 minutes. All samples recorded in Table I below were subjected to the third IOX step for 8 minutes in a 99.5% KNO3 / 0.5% NaNO3 salt bath.
[0297] Characterization after the second and third IOX steps included: washing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer; measuring warpage with a FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth. The total stress distribution and mechanical properties of each specimen were then calculated.
[0298] Table I
[0299]
[0300] Cross warp is measured along a line that is equal to the length of the edge of the specimen, extends through the center of the major surface of the specimen, and is parallel to the edge of the major surface, and is the difference between the maximum and minimum heights of the specimen surface along this line. Diagonal warp is measured along a line that extends diagonally between two corners and passes through the center of the major surface of the specimen, and is the difference between the maximum and minimum heights of the specimen surface along this line. Pre warp refers to the warp of the specimen before IOX treatment; final warp refers to the warp of the specimen after IOX treatment is completed.
[0301] Fig.12 and Fig.13The cross warping and diagonal warping of a 0.4 mm thick sample after each step of IOX treatment are shown in the figure, wherein two different salt compositions are used in the first IOX step. The salt concentrations used in the first IOX step are 40% NaNO3 / 60% KNO3 and 50%
[0302] NaNO3 / 50% KNO3, and the total salt weight was about 0.07g and about 0.1g respectively. A second IOX step was performed at 420°C for 2 hours using 100% KNO3, wherein the total salt weight was about 0.2g. A third IOX step was performed at 390°C for 8 minutes using 99.5% KNO3.
[0303] Fig.14 and Fig.15 The cross warping and diagonal warping of a 0.5 mm thick sample after each step of IOX treatment with different first IOX conditions are illustrated respectively. The salt concentrations used in the first IOX step were 40% NaNO3 / 60% KNO3 and 50% NaNO3 / 50% KNO3, respectively, and the total salt weight was approximately 0.07 g and approximately 0.1 g, respectively. Except for sample F3O, a second IOX step of 100% KNO3 was performed at a temperature of 420°C for 1.5 hours, wherein the total salt weight was approximately 0.18 g, and the second IOX step time of F3O was 2 hours. A third IOX step of 99.5% KNO3 was performed at a temperature of 390°C for 8 minutes. Sample F3J additionally included a heat treatment at 430°C for 6 hours between the first and second IOX steps.
[0304] Example 2
[0305] A glass product sample having the following composition: 63.60 mol% SiO2, 15.67 mol% Al2O3, 10.81 mol% Na2O, 1.16 mol% ZnO, 6.24 mol% Li2O, 0.04 mol% SnO2 and 2.48 mol% P2O5. The sample is in the form of a 2 inch x 2 inch square plate with a thickness of 0.5 mm or 0.8 mm.
[0306] The treatment used to obtain an asymmetric stress distribution using an initially flat specimen consisted of a three-step ion exchange. The specimens were rinsed with deionized (DI) water and then weighed to high precision specifications. The specimens were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the specimen surface could dry quickly and that there was no residual water on the resulting salt precipitate. The temperature of the specimen was estimated to be between about 80°C and 150°C. The actual number of sprays applied to the specimen surface depended on the weight of salt desired on the specimen. The number of sprays was 15 to 30. After the spraying was completed, the specimen was weighed again to determine the total weight gain of the salt. The total weight of the salt on the specimen was between 0.07g and 0.15g, depending on the salt composition used. The specimen was then placed in an oven at a temperature of 370°C with the coated side facing up for 0.5 to 1 hour. If the oven temperature was 390°C, the time was 1 to 2 hours. Also, when the samples were placed in the furnace, they were covered with a glass petri dish lid that was not in contact with the sample surface. The coated sample surface was recorded as the "back" surface, which had a negative warp and a convex shape.
[0307] The spray solution contained 100% KNO3 in deionized water. The total amount of salt used (by weight) was 58 g dissolved in 200 mL deionized water. The salt solution was prepared in a separate container and dissolved before it was pressed into the spray can to remove large particles of contaminants.
[0308] Heat treatment was also used after the first 10X step. Heat treatment was performed at 390°C for 1 hour, 1.5 hours and 2 hours. Heat treatment may cause warping, depending on the conditions used. Heat treatment has the effect of increasing the depth of compression.
[0309] Characterization after the first 10X step included: rinsing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer; weighing using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and depth of layer.
[0310] The second 10X step in the treatment is a double-sided ion exchange. Various salt compositions were used to perform the second 10X step for various times. The salt compositions used were 25% NaNO3 / 75% KNO3, 70% NaNO3 / 30% KNO3, and 49% NaNO3 / 51% KNO3. The various times used were 1.5 hours, 2 hours, 2.5 hours, 3.17 hours, 3.5 hours, and 3.67 hours. The sample was preheated for a total of 10 minutes in a chamber next to the bath at the same temperature as the bath. The sample was then immersed in the salt bath.
[0311] The third 10X step in the treatment was to stress spike both sides of the glass with a 94% KNO3 / 6% NaNO3 solution in an ion exchange bath at 380°C for 30 to 36 minutes. The sample was preheated in a chamber next to the bath for a total of 10 minutes at the same temperature as the bath.
[0312] Characterization after the second and third 10X steps included: washing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer; measuring warpage with a FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth. The total stress distribution and mechanical properties of each specimen were then calculated. The results for the specimens are recorded in Table II.
[0313] Table II
[0314]
[0315]
[0316] Fig.16 and Fig.17 The cross warping and diagonal warping of a 0.8 mm thick sample after each step of IOX treatment with different times in the second IOX step are shown respectively. The salt concentration used in the first IOX step was 100% KNO3, the temperature was 370°C, the time was 30 minutes, and the total salt weight was about 0.15g. The second IOX step used a salt concentration of 49% NaNO3 / 51% KNO3, the temperature was 380°C, and the times were 2.05 hours, 3.17 hours, and 3.66 hours. The third IOX step was performed at a temperature of 380°C for 36 minutes using 6% NaNO3 / 94% KNO3.
[0317] Fig.18 and Fig.19 The cross warping and diagonal warping of a 0.8 mm thick sample after each step of IOX treatment are shown. The first IOX step used a salt concentration of 100% KNO3, a temperature of 390°C, a time of 2 hours, and a total salt weight of about 0.15 g. The second IOX step used a salt concentration of 49% NaNO3 / 51% KNO3, a temperature of 380°C, and a time of 2 hours.
[0318] The third IOX step was carried out at a temperature of 380° C. for 30 minutes using NaNO 3 / 94% KNO 3. Sample F1I additionally included a heat treatment between the first and second IOX steps.
[0319] Fig. 20 and Fig.21The cross warp and diagonal warp of a 0.5 mm thick sample after each step of IOX treatment are shown respectively. The salt concentration used in the first IOX step was 100% KNO3, the temperature was 390°C, the time was 1 hour, and the total salt weight was about 0.15 g. The second IOX step used a salt concentration of 49% NaNO3 / 51% KNO3, the temperature was 380°C, and the time was 2.5 hours. The third IOX step was performed at a temperature of 380°C for 30 minutes using 6% NaNO3 / 94% KNO3. Sample F1M additionally included a heat treatment between the first and second IOX steps.
[0320] Fig. 22 and Fig.23 The cross warp and diagonal warp of a 0.5 mm thick sample after each step of IOX treatment are shown respectively. The salt concentration used in the first IOX step was 100% KNO3, the temperature was 390°C, the time was 1 hour, and the total salt weight was about 0.15 g. The second IOX step used a salt concentration of 49% NaNO3 / 51% KNO3, the temperature was 380°C, and the time was 1.5 hours. The third IOX step was performed at a temperature of 380°C for 30 minutes using 6% NaNO3 / 94% KNO3. Sample F1S additionally included a heat treatment between the first and second IOX steps.
[0321] Example 3
[0322] A glass product sample having the following composition: 63.60 mol% SiO2, 15.67 mol% Al2O3, 10.81 mol% Na2O, 1.16 mol% ZnO, 6.24 mol% Li2O, 0.04 mol% SnO2 and 2.48 mol% P2O5. The sample is in the form of a 2 inch x 2 inch square flat plate with a thickness of 0.5 mm.
[0323] The specimens were pre-warped in a large aluminum mold. The heat treatment program in the furnace was to increase the temperature to 570°C at a ramp rate of 20°C / minute, followed by holding the specimens at this temperature for 3 hours or 5 hours. These two temperatures were used in different treatments. Up to seven specimens were placed and fixed in the mold at one time. A carbon suspension was used to protect the mold from any puncture damage that the specimens might cause to the softer aluminum. The specimens were also shaped to round and smooth the edges to further protect the mold. Once pre-warped, the specimens were characterized by weighing them using a high-precision gauge and measuring the warpage using a profilometer. The convex side of the specimen was recorded as the "back" side.
[0324] The samples were subjected to a two-step IOX treatment. The two-step ion exchange treatment used to obtain an asymmetric distribution using an initially warped sample began with an initial single-sided bath with a certain salt concentration. 1% LiNO3 / 99% KNO3 and 2% LiNO3 / 98% KNO3 baths were used in the single-sided IOX step performed at 390°C. The baths were made in shallow round stainless steel containers. Before the IOX began, the samples were cleaned, weighed, and their warpage was measured. The pre-warped sample was placed into the bath with the convex side facing down using a small piece of metal mesh and flat-nose pliers. The salt only contacted the convex side of the sample. The time of the first IOX step was varied, including: 40 minutes, 50 minutes, 60 minutes, 72 minutes, and 90 minutes.
[0325] Characterization after the first 10X step included: rinsing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer; weighing using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and depth of layer.
[0326] The second IOX step was a double-sided exchange performed on both sides of the sample. Prior to the second ion exchange, the sample was preheated for 10 minutes in a furnace in a secondary container at the same temperature as the ion exchange bath (350° C.). Two different bath concentrations were used in this treatment, including 15% NaNO3 / 85% KNO3 and 25% NaNO3 / 75% KNO3. A variety of times were used to perform the above two second IOX step bath conditions, varying from 1 hour to 4 hours.
[0327] Characterization after the second IOX step included: washing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension with SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth. All measurements were used to determine the overall stress distribution and mechanical properties of each specimen.
[0328] Fig.24 and Fig.25 The cross warping and diagonal warping of a 0.5 mm thick pre-warped sample after each step of IOX treatment are shown separately. The sample was pre-warped by the following heat treatment: treatment at a temperature of 500°C for 2 hours in a spherical mold, followed by a temperature increase to a temperature of 560°C for 4.5 hours. The salt concentration used in the first IOX step was 1% LiNO3 and 99% KNO3, the temperature was 390°C, and the time was 50 minutes, 60 minutes, 72 minutes, and 90 minutes. The second IOX step used a salt concentration of 15% NaNO3 / 85% KNO3, the temperature was 350°C, and the time was 3 hours. Fig.24 and Fig.25 The initial condition shown in is a pre-warped glass article.
[0329] Fig.26 and Fig. 27 The cross warping and diagonal warping of a 0.5 mm thick pre-warped sample after each step of IOX treatment are shown separately. The sample was pre-warped by the following heat treatment: treatment at a temperature of 500°C for 2 hours in a spherical mold, followed by a temperature increase to a temperature of 560°C for 4.5 hours. The salt concentration used in the first IOX step was 1% LiNO3 and 99% KNO3, the temperature was 390°C, and the time was 72 minutes. The second IOX step used a salt concentration of 15% NaNO3 / 85% KNO3, the temperature was 350°C, and the time was 2 hours, 3 hours, and 4 hours. Fig.26 and Fig. 27 The initial condition shown in is a pre-warped glass article.
[0330] Example 4
[0331] A glass product sample having the following composition: 63.60 mol% SiO2, 15.67 mol% Al2O3, 10.81 mol% Na2O, 1.16 mol% ZnO, 6.24 mol% Li2O, 0.04 mol% SnO2 and 2.48 mol% P2O5. The sample is in the form of a 2 inch x 2 inch square flat plate with a thickness of 0.5 mm.
[0332] The first 10X step and pre-warping of the specimen in the mold were performed as in Example 3. The first 10X step was performed for 40 minutes, 50 minutes or 60 minutes.
[0333] The second IOX step performed was a double-sided exchange on both sides of the sample. The bath concentration used in the second IOX step was 49% NaNO3 / 51% KNO3. Two different ion exchange times were used: 1.25 hours and 1.67 hours. Prior to the second IOX step, the sample was preheated for 10 minutes in a furnace in a secondary container at the same temperature as the ion exchange (380°C).
[0334] A third IOX step was also used to produce compressive stress spikes on both sides of the sample. The third IOX step used a 4% NaNO3 / 96% KNO3 salt solution for 20 minutes at 380°C. Prior to the third IOX step, the sample was preheated in a furnace in a secondary container at the same temperature as the ion exchange (380°C) for 5 minutes.
[0335] Characterization after the second and third IOX steps included: washing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth. All measurements were used to determine the overall stress distribution and mechanical properties of each specimen.
[0336] Fig.28 and Fig.29 The cross warping and diagonal warping of a 0.5 mm thick pre-warped sample after each step of IOX treatment are shown separately. The sample was warped by heat treating in a spherical mold at a temperature of 570°C for 3 hours. The salt concentrations used in the first IOX step were 1% LiNO3 and 99% KNO3, the temperature was 390°C, and the times were 40 minutes, 50 minutes, and 60 minutes. The second IOX step used a salt concentration of 49% NaNO3 / 51% KNO3, the temperature was 380°C, and the time was 1 hour and 15 minutes. The third IOX step used a salt concentration of 4% NaNO3 / 96% KNO3, the temperature was 380°C, and the time was 20 minutes. Fig.28 and Fig.29 The initial condition shown in is a pre-warped glass article.
[0337] Example 5
[0338] A glass product sample having the following composition: 63.60 mol% SiO2, 15.67 mol% Al2O3, 10.81 mol% Na2O, 1.16 mol% ZnO, 6.24 mol% Li2O, 0.04 mol% SnO2 and 2.48 mol% P2O5. The sample is in the form of a 2 inch x 2 inch square flat plate with a thickness of 0.5 mm.
[0339] The specimens were pre-warped in a large aluminum mold. The heat treatment program in the mold was to increase the temperature to 500°C at a ramp rate of 20°C / minute and treat the specimens at this temperature for 2 hours. Additionally, the specimens were heated to 560°C at a ramp rate of 2°C / minute and treated at this temperature for 4.5 hours. In order to alleviate the initial warping, the final set temperature of the 4.5-hour treatment was changed to 540°C for some specimens. Up to seven specimens were placed in the mold at one time. A carbon suspension was used to protect the mold from any puncture damage that the specimens might cause to the softer aluminum. The specimens were also shaped to round and smooth the edges to further protect the mold. Once pre-warped, the specimens were characterized by weighing them using a high-precision gauge and measuring the warpage using a profilometer. The convex side of the specimen was recorded as the "back" side.
[0340] The samples were sprayed using a hot plate as described above. The total weight of salt on the samples ranged from 0.1 g to 0.2 g. The samples were then placed in an oven and covered as described above. The coated side was recorded as the "back" surface, which had a negative warp and a convex shape.
[0341] A three-step ion exchange treatment to obtain an asymmetric distribution was performed using initially warped specimens of 0.4 mm and 0.5 mm thickness. The salt compositions used for spraying included 100% KNO3 solution, 2% LiNO3 / 98% KNO3, and 4% LiNO3 / 96% KNO3. Single sprays with larger amounts of salt and double sprays with slightly smaller amounts of salt were attempted. Single and double sprays were successfully scaled up to larger parts using the same procedure but varying the mass of salt placed on the specimen. The two temperatures used in the first IOX step procedure included 370°C and 390°C. The time for the first IOX step ranged from 0.25 hours to 3 hours, depending on whether a single or double coating of the salt solution was used.
[0342] Characterization after the first 10X step included: rinsing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer; weighing using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and depth of layer.
[0343] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 49% NaNO3 / 51% KNO3. Two different IOX times were used: 3.8 hours and 4.5 hours. Prior to the ion exchange, the sample was preheated for 10 minutes in a furnace in a secondary container at the same temperature as the ion exchange (350°C).
[0344] The third 10X step is to use a salt concentration of 4% NaNO3 / 96% KNO3 to generate a double-sided stress distribution spike on both sides of the glass for 15 to 20 minutes. Before ion exchange, the sample is preheated for 5 minutes in a furnace in a secondary container at the same temperature as the ion exchange (380°C).
[0345] Characterization after the second and third IOX steps included: washing the specimens with deionized water to remove any residual salt; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth. All measurements were used to determine the overall stress distribution and mechanical properties of each specimen.
[0346] Table III below shows the various conditions used to treat the samples described above. These samples had the same final peak after treatment with 4% NaNO3 / 96% KNO3 at 380°C for 15 minutes.
[0347] Table III
[0348]
[0349] Fig.30 and Fig.31 The cross warping and diagonal warping of a 0.5 mm thick pre-warped specimen after each step of IOX treatment are shown separately. Fig.30 and Fig.31 The samples shown in are samples M6C, M6D and M6E described in Table III. Fig.30 and Fig.31 The initial condition shown in is a pre-warped glass article.
[0350] Example 6
[0351] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0352] The samples were washed with deionized (DI) water and then weighed with high precision specifications. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface could dry quickly and there was no residual water on the resulting salt precipitation. The temperature of the sample was estimated to be between about 80°C and 150°C. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays was 15 to 30. After the spraying was completed, the sample was weighed again to determine the total weight gain of the salt. Subsequently, the sample was placed in a furnace at 420°C for 1 hour with the coated side facing up to complete the first 10X step. And, when the sample was placed in the furnace, the sample was covered with a glass petri dish lid that was not in contact with the sample surface. The coated sample surface was recorded as the "back" surface, which has a negative warp and a convex shape. Therefore, the "front" surface has a concave shape.
[0353] The salt in the first 10X step was a coating formed from 100% tripotassium phosphate (TKP) precipitated by spraying a nearly saturated solution of TKP in deionized water. Two samples were prepared, the first having a total salt weight after drying of 0.563 g and the second having a total salt weight after drying of approximately 0.6 g.
[0354] Characterization after the first IOX step included: washing the specimens with deionized water to remove any residual salts; washing the specimens with a 5% acetic acid solution; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; performing weight measurement using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0355] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature as the ion exchange (380°C) for 15 minutes. The second IOX step resulted in a flipped sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0356] The third 10X step was a double-sided stress curve spike on both sides of the glass at 380° C. for 40 minutes using a salt concentration of 7% NaNO3 / 93% KNO3. Prior to ion exchange, the sample was preheated at 250° C. for 5 minutes, followed by an additional 5 minutes at 380° C. in a separate furnace. After the third 10X step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0357] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0358] The cross-warpage of the measured samples after each 10X step is shown in Fig.33 The cross warp measurements showed that the warp after the first 10X step was not repeatable for the first 10X salt composition. The cross warp measurements after the second and third 10X steps were substantially consistent. The measured diagonal warp after each 10X step was 1.88 to 2 times greater than the cross warp.
[0359] Example 7
[0360] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0361] The samples were washed with deionized (DI) water and then weighed with high precision specifications. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface could dry quickly and there was no residual water on the resulting salt precipitation. The temperature of the sample was estimated to be between about 80°C and 150°C. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays was 15 to 30. After the spraying was completed, the sample was weighed again to determine the total weight gain of the salt. Subsequently, the sample was placed in a furnace at 420°C for 1 hour with the coated side facing up to complete the first 10X step. And, when the sample was placed in the furnace, the sample was covered with a glass petri dish lid that was not in contact with the sample surface. The coated sample surface was recorded as the "back" surface, which has a negative warp and a convex shape. Therefore, the "front" surface has a concave shape.
[0362] The salt in the first 10X step was a coating of 99% tripotassium phosphate (TKP) and 1% KNO3, which was precipitated by spraying a nearly saturated solution of 99% by weight TKP and 1% by weight KNO3 in deionized water. Two samples were prepared, the first having a total salt weight after drying of 0.279 g and the second having a total salt weight after drying of approximately 0.412 g.
[0363] Characterization after the first IOX step included: washing the specimens with deionized water to remove any residual salts; washing the specimens with a 5% acetic acid solution; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; performing weight measurement using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0364] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature (380°C) as the ion exchange for 15 minutes. The second IOX step resulted in an undulating sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0365] The third IOX step was to produce double-sided spikes on both sides of the glass using a salt concentration of 7% NaNO3 / 93% KNO3 for 40 minutes at 380° C. The sample was preheated at 250° C. for 5 minutes before ion exchange in a separate furnace, followed by an additional 5 minutes at 380° C. After the third IOX step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0366] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0367] The cross-warpage of the measured samples after each 10X step is shown in Fig.34 The cross warp measurement results show that the warp after each 10X step is repeatable. The measured diagonal warp after each 10X step is 1.8 to 1.97 times larger than the cross warp.
[0368] Example 8
[0369] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0370] The samples were washed with deionized (DI) water and then weighed with high precision specifications. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface could dry quickly and there was no residual water on the resulting salt precipitation. The temperature of the sample was estimated to be between about 80°C and 150°C. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays was 15 to 30. After the spraying was completed, the sample was weighed again to determine the total weight gain of the salt. Subsequently, the sample was placed in a furnace at 420°C for 1 hour with the coated side facing up to complete the first 10X step. And, when the sample was placed in the furnace, the sample was covered with a glass petri dish lid that was not in contact with the sample surface. The coated sample surface was recorded as the "back" surface, which has a negative warp and a convex shape. Therefore, the "front" surface has a concave shape.
[0371] The salt in the first 10X step was a coating of 96% tripotassium phosphate (TKP) and 4% KNO3, which was precipitated by spraying a nearly saturated solution of 96% by weight TKP and 4% by weight KNO3 in deionized water. Two samples were prepared, the first having a total salt weight after drying of 0.403 g and the second having a total salt weight after drying of approximately 0.266 g.
[0372] Characterization after the first IOX step included: washing the specimens with deionized water to remove any residual salts; washing the specimens with a 5% acetic acid solution; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; performing weight measurement using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0373] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature (380°C) as the ion exchange for 15 minutes. The second IOX step resulted in an undulating sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0374] The third IOX step was to produce double-sided spikes on both sides of the glass using a salt concentration of 7% NaNO3 / 93% KNO3 for 40 minutes at 380° C. The sample was preheated at 250° C. for 5 minutes before ion exchange in a separate furnace, followed by an additional 5 minutes at 380° C. After the third IOX step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0375] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0376] The cross-warpage of the measured samples after each 10X step is shown in Fig.35 The cross warp measurement results show that the warp after each 10X step is repeatable. The measured diagonal warp after each 10X step is 1.89 to 1.99 times larger than the cross warp.
[0377] Example 9
[0378] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0379] The samples were cleaned with deionized (DI) water and then weighed with high precision specifications. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface can dry quickly and there is no residual water on the resulting salt precipitation. The temperature of the sample is estimated to be between about 80°C and 150°C. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays is 15 to 30 times. After the spraying is completed, the sample is weighed again to determine the total weight gain of the salt. Subsequently, the sample is placed in a furnace with the coated side facing up to complete the first 10X step. And, when the sample is placed in the furnace, the sample is covered with a glass petri dish lid that does not contact the sample surface. The coated sample surface is recorded as the "back" surface, which has a negative warp and a convex shape. Therefore, the "front" surface has a concave shape.
[0380] The salt in the first IOX step was a coating of 92% tripotassium phosphate (TKP) and 8% KNO3, which was precipitated by spraying a nearly saturated solution of 92% by weight TKP and 8% by weight KNO3 in deionized water. Eight samples were prepared, and their total salt weights after drying were 0.102 g, 0.205 g, 0.210 g, 0.408 g, 0.417 g, 0.468 g, 0.494 g, and 0.575 g, respectively. Except for the samples with total salt weights of 0.205 g and 0.468 g, the samples were subjected to the first IOX step at 420°C for 1 hour. The sample with a total salt weight of 0.205 g was subjected to the first IOX step at 390°C for 2 hours. The sample with a total salt weight of 0.468 g was subjected to the first IOX step at 420°C for 2 hours.
[0381] Characterization after the first IOX step included: washing the specimens with deionized water to remove any residual salts; washing the specimens with a 5% acetic acid solution; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; performing weight measurement using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0382] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature (380°C) as the ion exchange for 15 minutes. The second IOX step resulted in an undulating sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0383] The third IOX step was to produce double-sided spikes on both sides of the glass using a salt concentration of 7% NaNO3 / 93% KNO3 for 40 minutes at 380° C. The sample was preheated at 250° C. for 5 minutes before ion exchange in a separate furnace, followed by an additional 5 minutes at 380° C. After the third IOX step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0384] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0385] The cross-warpage of the measured samples after each 10X step is shown in Fig.36 The cross warp measurement results show that the warp after each IOX step is repeatable between each IOX condition. The measured diagonal warp after each IOX step is 1.86 to 2.1 times greater than the cross warp.
[0386] Example 10
[0387] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0388] The samples were cleaned with deionized (DI) water and then weighed with high precision specifications. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface can dry quickly and there is no residual water on the resulting salt precipitation. The temperature of the sample is estimated to be between about 80°C and 150°C. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays is 15 to 30 times. After the spraying is completed, the sample is weighed again to determine the total weight gain of the salt. Subsequently, the sample is placed in a furnace with the coated side facing up to complete the first 10X step. And, when the sample is placed in the furnace, the sample is covered with a glass petri dish lid that does not contact the sample surface. The coated sample surface is recorded as the "back" surface, which has a negative warp and a convex shape. Therefore, the "front" surface has a concave shape.
[0389] The salt in the first IOX step was a coating of 10% tripotassium phosphate (TKP) and 90% KNO3, which was precipitated by spraying a nearly saturated solution of 10 wt% TKP and 90 wt% KNO3 in deionized water. Three samples were prepared, and their total salt weights after drying were 0.106 g, 0.134 g, and 0.146 g, respectively. The first IOX step was performed at 420°C for 1 hour.
[0390] Characterization after the first IOX step included: washing the specimens with deionized water to remove any residual salts; washing the specimens with a 5% acetic acid solution; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; performing weight measurement using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0391] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature (380°C) as the ion exchange for 15 minutes. The second IOX step resulted in an undulating sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0392] The third IOX step was to produce double-sided spikes on both sides of the glass using a salt concentration of 7% NaNO3 / 93% KNO3 for 40 minutes at 380° C. The sample was preheated at 250° C. for 5 minutes before ion exchange in a separate furnace, followed by an additional 5 minutes at 380° C. After the third IOX step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0393] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0394] The cross-warpage of the measured samples after each 10X step is shown in Fig.37 The cross warp measurements showed that the warp after each 10X step was not repeatable. This was partly due to the fact that due to the low concentration of TKP, a capillary action of the salt from the back surface to the front surface of the specimen was observed in the first 10X step. The measured diagonal warp after each 10X step was 1.78 to 1.97 times greater than the cross warp.
[0395] Embodiment 11
[0396] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0397] The samples were washed with deionized (DI) water and then weighed with high precision. The samples were then placed on a hot plate set at 200°C to ensure that the salt solution sprayed on the sample surface could dry quickly and there was no residual water on the resulting salt precipitation. The temperature of the sample was estimated to be between about 80°C and 150°C. Before the salt solution was sprayed on the sample, a 40mm×40mm square of aluminum foil was placed in the center of the sample. This arrangement allows the salt to be deposited only on the periphery of the sample, which is an area extending 5mm from each edge of the surface. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays was 15 to 30 times. After the spraying was completed, the aluminum foil was removed from the sample and the sample was weighed again to determine the total weight gain of the salt. Subsequently, the sample was placed in a furnace with the coated side facing up to complete the first 10X step. And, when the sample was placed in the furnace, the sample was covered with a glass petri dish lid that did not contact the sample surface. The coated surface of the sample is recorded as the "back" surface, which has negative warpage and convex shape. Therefore, the "front" surface has a concave shape.
[0398] The salt in the first IOX step was a coating of 92% tripotassium phosphate (TKP) and 8% KNO3, which was precipitated by spraying a nearly saturated 92 wt% TKP and 8 wt% KNO3 solution in deionized water. Three samples were prepared, with total salt weights of 0.110 g, 0.111 g, 0.112 g, and 0.183 g after drying. Except for the sample with a total salt weight of 0.112 g, the samples were subjected to the first IOX step at 420°C for 1 hour. The sample with a total salt weight of 0.112 g was subjected to the first IOX step at 420°C for 2.42 hours.
[0399] Characterization after the first IOX step included: washing the specimens with deionized water to remove any residual salts; washing the specimens with a 5% acetic acid solution; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; performing weight measurement using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0400] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature (380°C) as the ion exchange for 15 minutes. The second IOX step resulted in an undulating sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0401] The third IOX step was to produce double-sided spikes on both sides of the glass using a salt concentration of 7% NaNO3 / 93% KNO3 for 40 minutes at 380° C. The sample was preheated at 250° C. for 5 minutes before ion exchange in a separate furnace, followed by an additional 5 minutes at 380° C. After the third IOX step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0402] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0403] The cross-warpage of the measured samples after each 10X step is shown in Fig.38. The measured cross warp after the third IOX step was between 8 μm and 28 μm. The measured diagonal warp after each IOX step was 1.26 to 3.63 times larger than the cross warp. The observed warp was concentrated on the periphery of the specimens, causing these specimens to exhibit significantly lower curvature than similar specimens in which the first IOX step was applied to the entire surface of the specimen. The cross warp range and the average value of the cross warp were at least one order of magnitude smaller than similar specimens in which the first IOX step was applied to the entire surface of the specimen.
[0404] Example 12
[0405] A glass product sample having the following composition: 63.76 mol% SiO2, 15.05 mol% Al2O3, 9.24 mol% Na2O, 2.37 mol% B2O3, 1.18 mol% ZnO, 5.88 mol% Li2O, 0.05 mol% SnO2 and 2.47 mol% P2O5. The sample was in the form of a 50 mm x 50 mm square plate with a thickness of 0.8 mm. The sample was subjected to a three-step ion exchange treatment.
[0406] The samples were cleaned with deionized (DI) water, wiped with a clean fabric soaked with acetone, and then weighed with high precision specifications. The samples were then placed on a hot plate set at 200°C to 250°C to ensure that the salt solution sprayed on the sample surface can dry quickly and there is no residual water on the resulting salt precipitation. The temperature of the sample is estimated to be between about 80°C and 150°C. The actual number of sprays on the sample surface depends on the weight of salt desired to be obtained on the sample. The number of sprays is 15 to 30 times. After the spraying is completed, the sample is weighed again to determine the total weight gain of the salt. Subsequently, the sample is placed in a furnace with the coated side facing up to complete the first 10X step. And, when the sample is placed in the furnace, the sample is covered with a glass petri dish lid that does not contact the sample surface. The coated sample surface is recorded as the "back" surface, which has a negative warp and a convex shape. Therefore, the "front" surface has a concave shape.
[0407] The salt in the first 10X step is a coating of the salts shown in Table IV below, which is precipitated by spraying a nearly saturated DI water solution. The solution is prepared by mixing the components and shaking to completely dissolve the salts. The solutions are then pressed into a spray can and a clean tissue is used to remove any large contaminant particles. The dried samples have a total salt weight of 0.1 g to 0.6 g.
[0408] Table IV
[0409] concentration TKP(g) <![CDATA[KNO3(g)]]> Water (mL) 10% TKP 1 9 35 25% TKP 2.5 7.5 30 50% TKP 5 5 23 80% TKP 8 2 20 92% TKP 9.2 0.8 14 96% TKP 9.6 0.4 12 99% TKP 9.9 0.1 12 100% TKP 18 0 20
[0410] The first IOX step was performed at 420°C for 1 hour.
[0411] Characterization after the first 10X step included: washing the specimens with deionized water to remove any residual salt; washing the specimens with a 5% acetic acid solution to remove coloration from salt precipitation; washing the specimens with deionized water; wiping the specimens with a tissue soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth. Depending on the degree of coloration, the time for the acetic acid wash ranged from about 30 minutes to about 3 hours. In some cases, the coloration could not be completely removed.
[0412] The second IOX step was a double-sided exchange performed on both sides of the sample. The salt concentration used in this treatment was 70% NaNO3 / 30% KNO3. The second IOX step was performed for 4 hours. Before the ion exchange, the sample was preheated in a furnace at the same temperature (380°C) as the ion exchange for 15 minutes. The second IOX step resulted in an undulating sample warp, so that the front surface had a convex shape, while the back surface had a concave shape.
[0413] The third IOX step was to produce double-sided spikes on both sides of the glass using a salt concentration of 7% NaNO3 / 93% KNO3 for 40 minutes at 380° C. The sample was preheated at 250° C. for 5 minutes before ion exchange in a separate furnace, followed by an additional 5 minutes at 380° C. After the third IOX step, the front surface of the sample had a convex shape, while the back surface had a concave shape.
[0414] Characterization after the second and third IOX steps included: rinsing the specimens with deionized water to remove any residual salt; wiping the specimens with a fabric soaked in acetone; measuring warpage with a profilometer and FlatMaster system; weighing using a high-precision gauge; measuring center tension using SCALP; and performing prism coupling measurements to determine compressive stress, inflection stress, and layer depth.
[0415] The results of the characterization are reported in Table V below. As shown in Table 5, increasing the amount of TKP as a solid component in the first IOX salt reduces the amount of surface dispersion. Similarly, increasing the amount of TKP also reduces the amount of reduction in compressive stress due to lithium poisoning.
[0416] Table V
[0417]
[0418] Although typical embodiments are given for illustration, the foregoing description should not be considered as limiting the scope of this specification or the appended claims. Therefore, various improvements, modifications and alternative forms may be conceived by those skilled in the art without departing from the spirit and scope of this specification or the appended claims.
Claims
1. A coated article comprising: A glass article comprising a first chemically strengthened surface layer and an opposing second chemically strengthened surface layer, wherein the first chemically strengthened surface layer is thinner than the second chemically strengthened surface layer; as well as A coating is disposed on the first chemically strengthened surface layer of the glass-ceramic.
2. The coated article of claim 1, wherein The glass article includes glass ceramics.
3. The coated article of claim 1 or 2, wherein: The coating is a compressive stress coating.
4. The coated article of claim 3, wherein: The compressive stress of the compressive stress coating is about 100 MPa to about 2000 MPa.
5. The coated article of claim 1 or 2, wherein: The coating includes aluminum oxynitride.
6. The coated article of claim 1 or 2, wherein: The coating was approximately 2 microns thick.
7. The coated article of claim 1 or 2, wherein: The compressive stress of the first chemically strengthened surface layer differs from the compressive stress of the second chemically strengthened surface layer by 30 MPa or more.
8. The coated article of claim 1 or 2, wherein: The first chemically strengthened surface layer has a first surface compressive stress, and the second chemically strengthened surface layer has a second surface compressive stress, wherein the second surface compressive stress is higher than the first surface compressive stress.
9. The coated article of claim 1 or 2, wherein: The glass article further includes a compressive stress of at least about 30 MPa at a depth less than 15% of a distance between the first chemically strengthened surface and the second chemically strengthened surface below the first chemically strengthened surface.
10. The coated article of claim 1 or 2, wherein: The glass product also includes: a first compressive stress layer extending from the first chemically strengthened surface to a first compressive depth in the glass article; a second compressive stress layer extending from the second chemically strengthened surface to a second compressive depth in the glass article; a first maximum compressive stress in the first compressive stress layer; and a second maximum compressive stress in the second compressive stress layer, Wherein a ratio of the first maximum compressive stress to the second maximum compressive stress is about 1:3 or less.
11. The coated article of claim 1 or 2, further comprising a compressive stress of at least about 500 MPa at a depth less than 10 μm below the second chemically strengthened surface.
12. The coated article of claim 1 or 2, further comprising a compressive stress of at least about 650 MPa at a depth of less than 5 μm below the second chemically strengthened surface.
13. The coated article of claim 1 or 2, further comprising a compressive stress of at least about 40 MPa at a depth less than 10% of the distance between the first chemically strengthened surface and the second chemically strengthened surface below the first chemically strengthened surface.
14. The coated article of claim 1 or 2, further comprising a compressive stress of at least about 30 MPa at a depth less than 15% of the distance between the first chemically strengthened surface and the second chemically strengthened surface below the first chemically strengthened surface.
15. A consumer electronic product comprising: a housing having a front surface, a back surface, and side surfaces; an electronic assembly provided at least partially within the housing, the electronic assembly including at least a controller, a memory, and a display, the display provided at or adjacent to a front surface of the housing; and A cover glass article disposed on the display, wherein at least one of a portion of the housing or the cover glass article comprises the coated article of claim 1 or 2.
Citation Information
Patent Citations
Asymmetric stress distribution in low warpage and high damage resistance glass products
CN115385584B